Degradable delivery particles made from redox initiator modified chitosan
By using the reaction product of crosslinking agent and modified chitosan as capsule shells, and treating chitosan with redox initiator, a biodegradable delivery particle with high structural integrity is formed, which solves the problem of premature release of delivery particles in the prior art, and achieves efficient delivery and good compatibility.
Patent Information
- Application Number
- CN202380062221.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-01
- Filing Date
- 2023-11-29
- Publication Date
- 2025-04-08
AI Technical Summary
The existing microcapsule technology is difficult to meet the requirements of biodegradability, low shell permeability, high deposition and target mechanical properties, especially in aqueous compositions containing surfactants or other carrier materials, and delivery particles are prone to premature release.
By using a reaction product of a crosslinker and modified chitosan as a capsule shell, chitosan is treated in conjunction with a redox initiator to form modified chitosan to form biodegradable delivery particles with high structural integrity.
The biodegradability and high structural integrity of the delivery particles are achieved, reducing leakage and resisting damage to the beneficial agents in the core by harsh environments, while improving compatibility with the finished matrix.
Smart Images

Figure CN119790131A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] Joint Research Statement
[0003] Encapsys, LLC and The Procter & Gamble Company entered into a joint research agreement on or about July 29, 2021, and the invention was made as a result of activities conducted between the parties within the scope of the joint research agreement in effect on or before the date of this invention. Technical Field
[0004] The present invention relates to a capsule manufacturing method and a biodegradable delivery particle produced by such a method, the delivery particle comprising a core material and a shell encapsulating the core, the shell comprising a reaction product of a cross-linking agent and a polysaccharide. Background Art
[0005] Microencapsulation is a method of encapsulating a droplet of a liquid, a solid particle or a gas in a solid shell and usually within the micrometer range. The core material is separated from the surrounding environment by a shell. Microencapsulation technology has a wide range of commercial applications in different industries. In general, capsules can carry out one or more of the following: (i) providing the stability of formulations or materials via mechanical separation of incompatible components, (ii) protecting the core material from the surrounding environment, (iii) masking or hiding the undesirable properties of active ingredients, and (iv) controlling or triggering the release of active ingredients to a specific time or position. All these attributes can lead to an increase in the shelf life of several products and the stability of active ingredients in liquid formulations.
[0006] Various processes and exemplary methods and materials for microencapsulation are described in Schwantes (U.S. Patent No. 6,592,990), Nagai et al. (U.S. Patent No. 4,708,924), Baker et al. (U.S. Patent No. 4,166,152), Wojciak (U.S. Patent No. 4,093,556), Matsukawa et al. (U.S. Patent No. 3,965,033), Ozono (U.S. Patent No. 4,588,639), Irgarashi et al. (U.S. Patent No. 4,610,927), Brown et al. (U.S. Patent No. 4,552,811), Scher (U.S. Patent No. 4,285,720), Jahns et al. (U.S. Patent Nos. 5,596,051 and 5,292,835), Matson (U.S. Patent No. 3,516,941), Foris et al.(U.S. Patent Nos. 4,001,140, 4,087,376, 4,089,802 and 4,100,103), Greene et al. (U.S. Patent Nos. 2,800,458, 2,800,457 and 2,730,456), Clark (U.S. Patent No. 6,531,156), Hoshi et al. (U.S. Patent No. 4,221,710), Hayford (U.S. Patent No. 4,444,699), Hasler et al. (U.S. Patent No. 5,105,823), Stevens (U.S. Patent No. 4,197,346), Riecke (U.S. Patent No. 4,622,267), Greiner et al. (U.S. Patent No. 4,547,429), and Tice et al. (U.S. Pat. No. 5,407,609) et al. and as taught by Herbig in the section entitled "Microencapsulation" in Kirk-Othmer Encyclopedia of Chemical Technology, Vol. 16, pp. 438-463.
[0007] Core-shell encapsulation can be used to preserve active agents (e.g., beneficial agents) in harsh environments and release them at a desired time, which may be during or after use of the article into which the encapsulate is incorporated. Among the various mechanisms that can be used to release beneficial agents from the encapsulate, the mechanism that is typically relied upon is mechanical rupture of the capsule shell by friction or pressure. The choice of mechanical rupture as a release mechanism poses another challenge to manufacturers because rupture must occur at a specific desired time, even if the capsule is subjected to mechanical stress before the desired release time.
[0008] Industrial interest in encapsulation technology has led to the development of several polymer capsule chemistries that attempt to meet the requirements of biodegradability, low shell permeability, high deposition, targeted mechanical properties and rupture profiles. Increased environmental concerns have put polymer capsules under scrutiny, so manufacturers have begun to investigate sustainable solutions for the encapsulation of beneficial agents.
[0009] Biodegradable materials exist and can be formed into delivery particles via coacervation, spray drying or phase inversion precipitation. However, delivery particles formed using these materials and techniques are highly porous and are not suitable for aqueous compositions containing surfactants or other carrier materials because the beneficial agent is released prematurely into the composition.
[0010] There are non-leaky and functional delivery particles in surfactant-based aqueous compositions, however due to their chemical nature and cross-linking they are not biodegradable.
[0011] Encapsulation can be found in various fields, such as medicine, personal care, textiles, food, coatings and agriculture. In addition, the major challenge faced by encapsulation is that the active agent to be encapsulated needs to be fully retained in the capsule throughout the entire supply chain until the controlled or triggered release of the core material is applied. Especially when it comes to small molecule encapsulation, there is a significantly limited microencapsulation technology that can meet the strict standards of long-term retention and active protection ability for commercial needs. In some applications and formulations, another challenge is the compatibility of delivery particles with finished substrates (such as laundry formulations or fabric care formulations). The stability in such a substrate is enhanced with the composition of the present invention.
[0012] There is a need for biodegradable delivery particles that still have high structural integrity, thereby reducing leakage and resisting damage from harsh environments. There is also a need for degradable delivery particles that have improved properties and are compatible with end-use formulations.
[0013] definition
[0014] As used herein, reference to the term "(meth)acrylate" or "(meth)acrylic" is understood to refer to both acrylate and methacrylate forms of the specified monomer, oligomer and / or prepolymer (e.g., "isobornyl (meth)acrylate" means that both isobornyl methacrylate and isobornyl acrylate are possible, similarly, reference to alkyl (meth)acrylates means that both alkyl acrylates and alkyl methacrylates are possible, and similarly, poly (meth)acrylates means that both polyacrylates and polymethacrylates are possible). Similarly, use of the phrase "prepolymer" means that the material referred to may exist as a prepolymer or a combination of oligomers and prepolymers. Similarly, it is understood that references to one or more (meth)acrylates in general herein, such as "water-soluble (meth)acrylates", "aqueous (meth)acrylates", etc., are intended to cover or include (meth)acrylate monomers and / or oligomers. Additionally, when referring to certain (meth)acrylate monomers and / or oligomers or initiators, the descriptors "water-soluble or water-dispersible," "water-soluble," and "water-dispersible" mean that the specified components are soluble or dispersible in a given matrix solution alone or in the presence of a suitable solubilizer or emulsifier, or when a certain temperature and / or pH is reached.
[0015] Unless otherwise indicated, each alkyl moiety herein may be C1-C8, or even C1-C 24Poly(meth)acrylate materials are intended to include a wide range of polymeric materials including, for example, polyester poly(meth)acrylates, urethane and polyurethane poly(meth)acrylates (especially those prepared by the reaction of hydroxyalkyl (meth)acrylates with polyisocyanates or urethane polyisocyanates), methyl cyanoacrylate, ethyl cyanoacrylate, diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, allyl (meth)acrylate, glycidyl (meth)acrylate, (meth)acrylate functionalized silicones, di-, tri- and tetraethylene glycol di(meth)acrylate. Acrylates, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, di(pentamethylene glycol) di(meth)acrylate, ethylene di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, bisphenol A di(meth)acrylate, diglycerol di(meth)acrylate, tetraethylene glycol dichloroacrylate, 1,3-butylene glycol di(meth)acrylate, neopentyl di(meth)acrylate, polyethylene glycol di(meth)acrylate and dipropylene glycol di(meth)acrylate as well as various multifunctional (meth)acrylates and multifunctional amine (meth)acrylates. Monofunctional acrylates (i.e., those containing only one acrylate group) can also be used advantageously. Typical monoacrylates include 2-ethylhexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, cyanoethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, p-dimethylaminoethyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, chlorobenzyl (meth)acrylate, aminoalkyl (meth)acrylate, various alkyl (meth)acrylates, and glycidyl (meth)acrylate. Of course, mixtures of (meth)acrylates or their derivatives and combinations of one or more (meth)acrylate monomers, oligomers and / or prepolymers or their derivatives with other copolymerizable monomers (including acrylonitrile and methacrylonitrile) may also be used. Multifunctional (meth)acrylate monomers will typically have at least two, at least three, and preferably at least four, at least five, or even at least six polymerizable functional groups.
[0016] For ease of reference in this specification and claims, the terms "monomer" or "monomers" as used herein with respect to the structural material forming the wall polymer of the delivery particle are to be understood as monomers, but also include oligomers and / or prepolymers formed from the specified monomers.
[0017] As used herein, the term "water-soluble material" means a material having a solubility in water at 60°C of at least 0.5% by weight.
[0018] As used herein, the term "oil-soluble" means a material having a solubility of at least 0.1 wt. % at 50°C in the core of interest.
[0019] As used herein, the term "oil dispersible" means a material that is dispersible at least 0.1 wt. % in the core of interest at 50°C without visible agglomerates.
[0020] As used herein, "delivery particle," "particle," "encapsulate," "microcapsule," and "capsule" are used interchangeably unless otherwise indicated. As used herein, these terms typically refer to a core / shell delivery particle. Summary of the invention
[0021] The present invention describes a population of core-shell delivery particles comprising a core material and a shell encapsulating the core material. The core comprises a beneficial agent and the shell comprises a polymeric material. The polymeric material is the reaction product of a crosslinking agent and a modified chitosan. The chitosan is a modified chitosan wherein the chitosan is treated with a redox initiator under acidic conditions resulting in unique properties in the polymeric material. The modified chitosan may be further treated with additional acid. "Core-shell encapsulate" and "delivery particle" may be used interchangeably when referring to the core-shell delivery particle population herein.
[0022] The compositions and manufacturing methods of the present invention enable delivery particles that are compatible with finished substrates (e.g., laundry formulations or fabric care formulations). The stability within such substrates is enhanced with the compositions of the present invention. Compatibility is determined by examining the degree of agglomeration, which is measured by the increase in aggregate particle size in a representative substrate. The delivery particles of the present invention are able to achieve compatibility while also meeting biodegradability requirements, yet still have high structural integrity, thereby reducing leakage and resisting damage to the beneficial agent in the core from harsh environments.
[0023] The present invention teaches delivery particles that are improved in at least one property category, and preferably more than one property category, particularly the categories of leakage, degradability, and compatibility. Compatibility is determined in terms of compatibility with laundry substrates, measured as described herein. In an embodiment, the delivery particles are described as having improved leakage and degradability and compatibility with the substrate.
[0024] The redox initiator is selected from persulfate or peroxide. Preferably, the redox initiator is selected from ammonium persulfate, sodium persulfate, potassium persulfate, cesium persulfate, benzoyl peroxide, hydrogen peroxide, and mixtures thereof. Chitosan is modified by treating chitosan with a redox initiator under acidic conditions and depolymerizing chitosan to an average molecular weight of 1-600 kDal., preferably 5-300 kDal., more preferably 30-100 kDal. Surprisingly, chitosan treated with a redox initiator simultaneously or sequentially results in unexpectedly higher performance encapsulates with enhanced degradability. Acid and redox initiator treatment reduces viscosity and makes it easy to handle. A combination of acid and redox initiator treatment can be achieved in the aqueous phase or by adding a redox initiator to the emulsion. Chitosan can be modified with a redox initiator in the aqueous phase or chitosan can be added to the emulsion with a redox initiator to modify, or added to both. Chitosan can be acid-treated in an aqueous phase, followed by modifying the acid-treated chitosan in an emulsion. Chitosan can be modified with a redox initiator in an aqueous phase under acidic conditions, followed by further adding a redox initiator to the emulsion. When chitosan is treated with a redox initiator, chitosan becomes modified chitosan.
[0025] Surprisingly, the shells of the novel core-shell encapsulates taught herein are degradable at a rate that satisfies the requirements of test methods such as OECD 301 B. The present invention teaches that the encapsulates are capable of degrading by at least 40% within 60 days when tested according to test method OECD 301 B.
[0026] Surprisingly, the acid and redox initiator treated delivery particles have better compatibility in matrices such as laundry detergents than the acid only treated delivery particles.
[0027] In some embodiments, the chitosan is initially acid treated and then modified with a redox initiator to form a modified chitosan. The acid-treated chitosan comprises a hydrolyzate produced by treating chitosan with an acid or with a mixture of a first acid and a second acid. The first acid comprises a strong acid and the second acid comprises a weak acid, wherein the chitosan is treated for a period of time at a pH of 6.5 or less, or even less than pH 6.5, or even at a pH of 3-6.2, or even at a pH of 5-6.2, and at a temperature of at least 25°C to obtain a treated chitosan solution having a viscosity of less than 1500cp and preferably a viscosity of less than 500cp. Such a period of time for treatment is typically at least one hour. In the method of the present invention, the first acid and the second acid are present in a normality ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35. In an embodiment, at least 21% by weight of the shell consists of a structural moiety derived from the acid-treated chitosan (further treated with a redox initiator). The first acid is a strong acid and may be selected from hydrochloric acid, perchloric acid, nitric acid, sulfuric acid and mixtures thereof. Such acid-treated chitosan may be further treated with a redox initiator to form an acid-treated modified chitosan.
[0028] Modified chitosan is formed by treating chitosan with a redox initiator. In various embodiments, this may include chitosan treated with an acid and a redox initiator. The method may include forming a hydrolyzate produced by treating chitosan with an acid or a mixture of a first acid and a second acid, and a redox initiator in any order. The redox initiator forms modified chitosan. The treatment of chitosan and / or modified chitosan may include acid treatment, preferably with a first acid comprising a strong acid, and a second acid comprising a weak acid, wherein the chitosan is treated at a pH of 6.5 or less, or even less than pH 6.5, or even at a pH of 3-6.2, or even at a pH of 5-6.2, and at a temperature of at least 25°C for a period of time to obtain a treated chitosan solution having a viscosity of less than 1500cp and preferably less than 500cp viscosity. Such a period of time for treatment is typically at least one hour. In the method of the present invention, the first acid and the second acid are present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35. In an embodiment, at least 21% by weight of the shell consists of moieties derived from chitosan modified with a redox initiator, or acid treated and redox initiator modified chitosan (optionally further modified with the same or different redox initiator in the emulsion). The first acid is a strong acid and may be selected from hydrochloric acid, perchloric acid, nitric acid, sulfuric acid and mixtures thereof.
[0029] The second acid is an organic acid selected from the group consisting of formic acid, acetic acid, ascorbic acid, glutamic acid, lactic acid, maleic acid, malic acid, succinic acid, citric acid, acrylic acid, oxalic acid, tartaric acid, and mixtures thereof.
[0030] In an embodiment, the first acid has a first pKa of less than 1, and the second acid has a first pKa of 5.5 or less. Because the acid can be dibasic or polybasic, it is understood that such an acid has a first pKa and an additional pKa (based on the additional acid groups). For clarity herein, the first pKa of each dibasic or polybasic acid is used as a selection parameter.
[0031] The redox initiator used to modify chitosan is a persulfate or a peroxide. The redox initiator can be selected from ammonium persulfate, sodium persulfate, potassium persulfate, cesium persulfate, benzoyl peroxide and hydrogen peroxide. The persulfate or peroxide contains 0.1-99% by weight of chitosan. The weight ratio of the redox initiator to the chitosan is 90 / 10 to 0.01 / 99.99, preferably 50 / 50 to 1 / 99, more preferably 30 / 70 to 3 / 97. When persulfate is used, it is believed that the sulfate group is ionically bound to the amino group of chitosan. The shell of the delivery particle may contain sulfur atoms, which can be generated, for example, by the interaction between the sulfur-containing redox initiator (e.g., persulfate compound) and chitosan. The sulfur atom can be present in the shell at a level of about 0.1% to about 20%, more preferably about 0.1% to about 10%, and even more preferably about 0.1% to about 1%, based on the weight of the shell. The presence and amount of sulfur atoms can be determined by energy dispersive X-ray microanalysis according to the EDX method provided in the Test Methods section below.
[0032] In a method of preparing a core-shell delivery particle population, the core comprises a beneficial agent and the shell comprises a polymeric material which is the reaction product of a crosslinking agent (e.g., a polyisocyanate) and modified chitosan or acid-treated chitosan and a redox initiator. The method comprises providing an aqueous phase by dissolving or dispersing chitosan, a redox initiator, and a first acid in an aqueous solution in any order.
[0033] The pH of the aqueous phase is adjusted to a pH of 6.5 or less, or even less than pH 6.5, or even a pH of 3-6.2, or even a pH of 5-6.2 by adding at least a first acid and a redox initiator, and heated to a temperature of at least 25°C to form a hydrozylate comprising chitosan treated with an acid and modified with a redox initiator.
[0034] The oil phase is formed, comprising the step of dissolving together at least one benefit agent and at least one polyisocyanate, optionally with added oil.
[0035] The emulsion is formed by mixing the aqueous phase and the oil phase in excess aqueous phase under high shear agitation, thereby forming droplets of the oil phase and the benefit agent dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to within the range of pH 3 to pH 6. Optionally, a second redox initiator is added to the emulsion at the grinding temperature or at an elevated temperature.
[0036] The emulsion is cured by heating to at least 40°C for a time sufficient to form a shell at the interface of the droplet with the aqueous phase, the shell comprising the reaction product of a polyisocyanate and acid-treated and redox initiator-treated chitosan, and surrounding a core comprising droplets of the oil phase and the benefit agent.
[0037] Preferably, at least 21 wt% of the shell comprises acid treated and redox initiator modified chitosan. The redox initiator is selected from persulfates or peroxides. A second redox initiator (same or different to the first redox initiator) may be added to the emulsion.
[0038] Additionally, the second acid can be added to the aqueous phase. It may be advantageous to select the first acid as a strong acid and the second acid as a weak acid. Desirably, the first acid and the second acid are present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35.
[0039] In other configurations, the delivery particles of the present invention can be made into new articles by incorporating into various articles. Such articles can be selected from agricultural formulations, slurries encapsulating agricultural active agents, populations of dry delivery particles encapsulating agricultural active agents, agricultural formulations encapsulating pesticides, and agricultural formulations for delivering pre-emergence herbicides. The agricultural active agent can be selected from agricultural herbicides, agricultural pheromones, agricultural pesticides, agricultural nutrients, insect control agents, and plant stimulants. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Digital image showing delivered particles.
[0041] Figure 2 Each phase is shown in relation to the intensity of each peak measured using the EDX method.
[0042] Figure 3 Displays the EDX spectrum of a given sample.
[0043] Figure 4 A delivery particle according to the present invention is described. Figure 4The charge differences of the encapsulates are described, which compare acid treatment and the addition of a redox initiator to the aqueous phase or to the emulsion, as described in the examples. As shown in the examples, the present invention enables the customization of the zeta potential. The present invention achieves a reduction or moderation of the zeta potential under the pH conditions used, resulting in a more controllable encapsulate that is usefully less prone to agglomeration in end-use applications and more compatible with the matrix. DETAILED DESCRIPTION
[0044] The present invention describes a delivery particle comprising a core material and a shell encapsulating the core material. The core material may comprise a beneficial agent. The shell comprises a polymer.
[0045] The present invention describes a composition comprising a delivery particle having a shell made at least in part from a chitosan-based material. More particularly, the shell comprises chitosan that has been treated with a redox initiator such as a persulfate or peroxide. The chitosan may also be treated with an acid. The resulting modified chitosan is then reacted with a crosslinking agent to form the shell of the delivery particle. "Modified chitosan" is understood to be chitosan treated with a redox initiator.
[0046] The delivery particle has a shell made at least in part of a chitosan-based material. The shell is a reaction product of a crosslinker (e.g., a polyisocyanate) and an acid-treated chitosan (which is further treated with a redox initiator (e.g., a persulfate or peroxide). The redox initiator forms a modified chitosan. To form the modified chitosan, the redox initiator can be added to the aqueous phase, to the emulsion, or to both. In particular, the delivery particle includes a shell comprising the reaction product of chitosan and a crosslinker. In an embodiment, the chitosan is characterized in that it has been treated with an acid. In an alternative embodiment, the acid is a mixture of a first acid and a second acid, the first acid comprising a strong acid and the second acid comprising a weak acid. The acid-treated chitosan is also treated with a redox initiator to form a modified chitosan. It is seen that the acid treatment results in an increase in the average molecular weight within a specific range, and also produces a surprising reduction in the viscosity of the treated chitosan. It is seen that the redox initiator depolymerizes the chitosan, thereby further reducing the viscosity of the treated chitosan.
[0047] In particular, the present invention comprises a composition comprising a core-shell encapsulate. The core comprises a beneficial agent. The shell comprises a polymeric material which is the reaction product of a crosslinking agent (e.g., a polyisocyanate) and a modified chitosan (chitosan treated with a redox initiator), or an acid-treated chitosan together with a redox initiator (modified chitosan also treated with acid). The redox initiator may be selected from a persulfate or a peroxide. The acid-treated chitosan forms a hydrolyzed chitosan.
[0048] It is believed that it is also advantageous to treat chitosan under acidic conditions. Acidic conditions can improve the solubility of chitosan, thereby making it more useful for reacting with a redox initiator to form modified chitosan. It is also believed that acidic conditions can affect the molecular weight and / or structure of chitosan, resulting in improved particles and / or performance.
[0049] For example, the modified chitosan can be formed under acidic conditions at a temperature of at least 25°C, preferably at a pH of 6.5 or less, preferably less than 6.5, even more preferably at a pH of about 3 to about 6.2, more preferably about 5 to about 6.2.
[0050] Chitosan (which may be referred to as original chitosan or parent chitosan before being modified by acid treatment and / or treatment with a redox initiator) may be treated with acid, preferably at a temperature of about 25°C to about 99°C, preferably about 75°C to about 95°C, at a pH of 6.5 or less, for at least one hour, preferably about one hour to about three hours, or for a period of time required to obtain a chitosan solution viscosity of not more than about 1500 cps, or even not more than 500 cps, of the acid-treated chitosan.
[0051] The modified chitosan (chitosan treated with a redox initiator) may be an acid-treated modified chitosan. For example, the chitosan may be treated with an acid. The acid may comprise a weak acid. The acid preferably comprises a mixture of acids, more preferably a mixture of a first acid and a second acid, wherein the first acid is a strong acid and wherein the second acid is a weak acid. Preferably, the first acid and the second acid are present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35. The first acid may have a first pKa of less than 1, and the second acid may have a first pKa of 5.5 or less. Preferably, the second acid has a first pKa of 1-5.5.
[0052] The first acid may comprise, consist essentially of, or consist of a strong acid selected from the group consisting of hydrochloric acid, perchloric acid, nitric acid, sulfuric acid, and mixtures thereof, preferably hydrochloric acid. The second acid may comprise, consist essentially of, or consist of a weak acid selected from the group consisting of formic acid, acetic acid, ascorbic acid, glutamic acid, lactic acid, maleic acid, malic acid, succinic acid, citric acid, acrylic acid, oxalic acid, tartaric acid, and mixtures thereof, preferably formic acid, acetic acid, and mixtures thereof.
[0053] Before modification (i.e. before treatment with a redox initiator), chitosan may be treated with an acid. However, for at least a portion of the treatment process, it may be convenient to simultaneously treat chitosan with a redox initiator and an acid. For example, chitosan may be dissolved or dispersed in an acidic aqueous phase, and a redox initiator may be added after dissolution / dispersion. Alternatively, an acid and a redox initiator may be provided to the aqueous phase (in any suitable order), and then the chitosan may be added and dissolved / dispersed.
[0054] It is believed that selecting chitosan and / or modified chitosan with a specific molecular weight can contribute to improved processability, performance and / or biodegradability. Relatively too large chitosan can result in a solution with a high viscosity that is difficult to process. Relatively too small chitosan can result in poor shell formation, which may be due to the increased solubility of chitosan causing chitosan to be less likely to migrate to the water / oil interface during shell formation.
[0055] Prior to treatment with a redox initiator and / or acid, preferably at least prior to treatment with a redox initiator, the chitosan may be characterized by a weight average molecular weight of about 100 kDa to about 600 kDa, preferably about 100 kDa to about 500 kDa, more preferably about 100 kDa to about 400 kDa, more preferably about 100 kDa to about 300 kDa, even more preferably about 100 kDa to about 200 kDa.
[0056] After treatment with a redox initiator and / or an acid, preferably at least after treatment with a redox initiator, the modified chitosan may be characterized by a weight average molecular weight of about 1 kDa to about 600 kDa, preferably about 5 kDa to about 300 kDa, more preferably about 10 kDa to about 200 kDa, more preferably about 15 kDa to about 150 kDa, even more preferably about 20 kDa to about 100 kDa. The modified chitosan may be characterized by a weight average molecular weight of about 1 kDa to about 600 kDa, preferably about 5 kDa to about 300 kDa, more preferably about 30 kDa to about 100 kDa.
[0057] Chitosan can be characterized by a degree of deacetylation of at least 50%, preferably about 50% to about 99%, more preferably about 75% to about 90%, and even more preferably about 80% to about 85%. The degree of deacetylation can affect the solubility of chitosan, which in turn can affect its reactivity or behavior during the formation of the particle shell. For example, too low a degree of deacetylation (e.g., less than 50%) results in relatively insoluble and relatively unreactive chitosan. A relatively high degree of deacetylation can result in very soluble chitosan, resulting in relatively little chitosan moving to the oil / water interface during shell formation.
[0058] Chitosan can also be modified with charged moieties. For example, before or after treatment with a redox initiator, the chitosan can comprise anionically modified chitosan, cationically modified chitosan, or a combination thereof. Modifying chitosan anionically and / or cationically can alter the properties of the shell of the delivery particle, for example by changing the surface charge and / or zeta potential, which can affect the deposition efficiency and / or formulation compatibility of the particle. For example, the modified chitosan can be further modified with a modifying compound, wherein the modifying compound comprises an epoxide, an aldehyde, an α,β-unsaturated mixture, or a combination thereof.
[0059] The redox initiator modifies the chitosan and depolymerizes the chitosan to an average molecular weight of 1-600 kDal. The reduction in molecular weight helps improve the workability of the chitosan by reducing viscosity. Acid treatment itself increases molecular weight but surprisingly reduces viscosity. The redox initiator further reduces viscosity, beneficially making the material more versatile for use in the shell forming encapsulation process.
[0060] When tested according to test method OECD 301 B, the shell of the core-shell encapsulate degrades by at least 40% within 60 days.
[0061] The acid-treated modified chitosan is produced by treating chitosan with an acid and modifying it with a redox initiator, preferably a mixture of a first acid and a second acid. The first acid comprises a strong acid, and the second acid comprises a weak acid. The chitosan is treated at a pH of 6.5 or less, or even less than pH 6.5, or even at a pH of 3-6.2, or even at a pH of 5-6.2, and at a temperature of at least 25°C for at least about one hour, more particularly for a period of time to obtain a treated chitosan solution having a viscosity of less than 1500cp and preferably a viscosity of less than 500cp. Such a period of time for treatment is typically at least one hour.
[0062] The first acid and the second acid are present in a normality ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35. At least 21 wt. % of the shell consists of moieties derived from acid-treated chitosan.
[0063] The first acid is a strong acid selected from the group consisting of hydrochloric acid, perchloric acid, nitric acid, sulfuric acid, and mixtures thereof. The second acid is an organic acid selected from the group consisting of formic acid, acetic acid, ascorbic acid, glutamic acid, lactic acid, maleic acid, malic acid, succinic acid, citric acid, acrylic acid, oxalic acid, tartaric acid, and mixtures thereof.
[0064] The first acid has a first pKa of less than 1, and the second acid has a first pKa of 5.5 or less. Preferably, the second acid has a first pKa of 1-5.5.
[0065] The redox initiator is selected from the group consisting of ammonium persulfate, sodium persulfate, and potassium persulfate, cesium persulfate, benzoyl peroxide, and hydrogen peroxide. A combination of initiators may optionally be employed.
[0066] The ratio of persulfate or peroxide to original chitosan is 0.01 / 99.99 to 95 / 5 by weight.
[0067] Crosslinking agents, preferably polyisocyanates, are understood herein to encompass monomers, oligomers and prepolymers selected from any aliphatic or aromatic isocyanate, including by way of illustration and not limitation: polyisocyanurates of toluene diisocyanate, trimethylolpropane adducts of toluene diisocyanate, trimethylolpropane adducts of xylylene diisocyanate, methylene diphenyl isocyanate, toluene diisocyanate, [diisocyanato(phenyl)methyl]benzene, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate, phenylene diisocyanate, their derivatives and mixtures thereof.
[0068] The core-shell encapsulate has a core to shell ratio of up to 99: 1, or even 99.5: 0.5 by weight. The benefit agent is preferably a perfume or fragrance, but may be selected from any of the following: perfumes, fragrances, agricultural actives, phase change materials, essential oils, lubricants, colorants, preservatives, antimicrobial actives, antifungal actives, herbicides, antiviral actives, preservative actives, antioxidants, bioactives, deodorants, emollients, moisturizers, exfoliants, UV absorbers, corrosion inhibitors, silicone oils, waxes, bleaching particles, fabric conditioners, malodor reducing agents, dyes, optical brighteners, antiperspirant actives, and mixtures thereof.
[0069] The core-shell delivery particles may have a median particle size of from 1 to 200 or even to 300 microns. Particle sizes of the encapsulates of 1-100 microns are preferred.
[0070] Described in the Examples and Figure 1 The delivery particles according to the invention shown in are cationic, having a zeta potential of at least 1 mV or even 15 mV at a pH of 4.5.
[0071] For the delivery particles as taught herein, the shell degrades by at least 40% of its mass after at least 60 days when tested according to test method OECD 301 B.
[0072] Without wishing to be bound by theory, it is believed that careful selection of the molecular weight of the chitosan may be advantageous. For example, selecting chitosan having a molecular weight above a certain threshold may result in delivery particles that perform better at some contact points than particles made from chitosan of lower molecular weight. In addition, selecting chitosan characterized by a relatively high molecular weight may result in processing challenges because such chitosans tend to increase viscosity, particularly in aqueous environments; the relatively high viscosity may affect the convenient flowability of such solutions and / or inhibit the full formation of the particle wall. Surprisingly, treatment with an acid and a redox initiator produced chitosans in which the average weight was reduced by about 5 kDal to about 300 kDal. It is seen that combination with a redox initiator (particularly a persulfate) depolymerizes the particle wall material, further reducing viscosity and enabling easy processing.
[0073] The chitosans, delivery particles, treatment compositions and related methods of the present disclosure are discussed in more detail below.
[0074] The present invention teaches a composition comprising a core-shell encapsulate. The core comprises a beneficial agent, preferably a fragrance, and the shell comprises a polymeric material which is the reaction product of a crosslinking agent and a modified chitosan. In forming the composition of the present invention, chitosan is treated with a mixture of a first acid and a second acid and modified with a redox initiator, the first acid comprising a strong acid and the second acid comprising a weak acid. Chitosan is treated with a mixture of acids and a redox initiator at a pH of 6.5 or less, or even less than pH 6.5, or even at a pH of 3-6.2, or even at a pH of 5-6.2, and at a temperature of at least 25°C for at least one hour, or for a period of time to obtain a treated chitosan solution having a viscosity of less than 1500 cp and preferably a viscosity of less than 500 cp. Such a period of time for treatment is typically at least one hour.
[0075] The first acid of the acid mixture and the second acid of the acid mixture are present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35. In the composition, it is desirable that at least 21 wt. % of the crust consists of moieties derived from acid-treated chitosan.
[0076] The first acid of the acid mixture is a strong acid selected from the group consisting of hydrochloric acid, perchloric acid, nitric acid, sulfuric acid and even mixtures thereof. The second acid is an organic acid selected from the group consisting of formic acid, acetic acid, ascorbic acid, glutamic acid, lactic acid, maleic acid, malic acid, succinic acid, citric acid, acrylic acid, oxalic acid, tartaric acid and mixtures thereof.
[0077] The first acid may be selected to have a pKa less than 1, and the second acid pKa is 5.5 or less, preferably a pKa of 1-5.5. The acid may be monobasic, dibasic or polybasic. It is understood that a dibasic, tribasic or polybasic acid will have more than one ionizable hydrogen, and therefore have a first or initial pKa and additional pKa values for additional ionizable hydrogens, respectively. For purposes of the present invention, when the acid is dibasic or polybasic, the first pKa refers to the first or initial ionizable hydrogen.
[0078] The shell may comprise from 1 to 25 wt % of the core-shell encapsulate.
[0079] The crosslinking agent of the composition can be selected from the following: polyisocyanurate of toluene diisocyanate, trimethylolpropane adduct of toluene diisocyanate, trimethylolpropane adduct of xylylene diisocyanate, methylene diphenyl diisocyanate, [diisocyanato(phenyl)methyl]benzene, toluene diisocyanate, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate, and phenylene diisocyanate, their derivatives and their combinations.
[0080] When formulated according to the teachings of the present invention, the shell degrades by at least 40% or even at least 60% of its mass after at least 60 days when tested according to test method OECD 301 B.
[0081] The core-shell encapsulate has a core to shell ratio of at least 75:25, or even up to 99:1, or even at least 99.5:0.5 by weight.
[0082] The benefit agent is selected from the group consisting of fragrances, flavors, agricultural actives, phase change materials, essential oils, lubricants, colorants, preservatives, antimicrobial actives, antifungal actives, herbicides, antiviral actives, preservative actives, antioxidants, bioactives, deodorants, emollients, moisturizers, exfoliants, UV absorbers, corrosion inhibitors, silicone oils, waxes, bleaching particles, fabric conditioners, malodor reducers, dyes, optical brighteners, antiperspirant actives, and mixtures thereof.
[0083] Also described is a method of preparing a core-shell delivery particle population, the core comprising a beneficial agent, the shell comprising a polymeric material, the polymeric material being the reaction product of a crosslinker and a modified chitosan or an acid-treated chitosan and a redox initiator. The method comprises forming an aqueous phase by treating chitosan with an acid, preferably a mixture of a first acid and a second acid, and modifying the chitosan with a redox initiator, the first acid comprising a strong acid, and the second acid comprising a weak acid, wherein the chitosan is treated at a pH of 6.5 or less, or even less than pH 6.5, or even at a pH of 3-6.2, or even at a pH of 5-6.2, and a temperature of at least 25° C. for at least one hour, or a viscosity of 1500 cps or even 500 cps, wherein the first acid and the second acid are present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35, and thereby forming the acid-treated chitosan.
[0084] The steps also include: forming an oil phase, including dissolving together at least one benefit agent and at least one crosslinking agent, preferably a polyisocyanate, optionally with added oil;
[0085] forming an emulsion by: mixing an aqueous phase and an oil phase in an excess of the aqueous phase under high shear agitation, thereby forming droplets of the oil phase and the benefit agent dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to within the range of pH 3 to pH 6;
[0086] The emulsion is solidified by heating to at least 40°C for a time sufficient to form a shell at the interface of the droplet with the aqueous phase, the shell comprising the reaction product of the crosslinker and the acid treated and redox initiator modified chitosan, and surrounding a core comprising droplets of the oil phase and the benefit agent.
[0087] Also described is a method of preparing a population of delivery particles, wherein the delivery particles comprise a core and a shell surrounding the core. In particular, the method comprises the following steps:
[0088] forming an aqueous phase by treating chitosan with a redox initiator in the presence of water at a pH of 6.5 or less and a temperature of at least 25° C., preferably for at least one hour and / or until the aqueous phase is characterized by a viscosity of less than 1500 cp, preferably less than 500 cp, to form a modified chitosan,
[0089] forming an oil phase, said forming step comprising dissolving together at least one benefit agent and at least one crosslinking agent, preferably a polyisocyanate, optionally with added oil, preferably a partitioning modifier;
[0090] forming an emulsion by mixing an oil phase in an excess of an aqueous phase, preferably under high shear agitation, thereby forming droplets of the oil phase dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to within the range of pH 2 to pH 6;
[0091] Optionally, a second redox initiator is provided to the emulsion to further form the modified chitosan. The second redox initiator may be the same as or different from the redox initiator added to the aqueous phase;
[0092] The emulsion is cured at a temperature of at least 40°C for a time sufficient to form a shell at the interface of the droplets with the aqueous phase. The shell comprises the reaction product of a crosslinker and modified chitosan. The shell surrounds a core comprising droplets of the oil phase.
[0093] In a variation of the method, a method of preparing a population of delivery particles is described, wherein the delivery particles comprise a core and a shell surrounding the core, the method comprising the steps of:
[0094] forming an aqueous phase by treating chitosan in the presence of water at a pH of 6.5 or less and a temperature of at least 25° C., preferably for at least one hour and / or until the aqueous phase is characterized by a viscosity of less than 1500 cp, preferably less than 500 cp,
[0095] forming an oil phase, said forming step comprising dissolving together at least one benefit agent and at least one crosslinking agent, preferably a polyisocyanate, optionally with added oil, preferably a partitioning modifier;
[0096] forming an emulsion by mixing an oil phase in an excess of an aqueous phase, preferably under high shear agitation, thereby forming droplets of the oil phase dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to within the range of pH 2 to pH 6;
[0097] adding a redox initiator to the emulsion to form modified chitosan, and
[0098] The emulsion is solidified at a temperature of at least 40°C for a time sufficient to form a shell at the interface of the droplets with the aqueous phase.
[0099] The shell comprises the reaction product of a cross-linking agent and modified chitosan. The shell surrounds a core comprising droplets of an oil phase.
[0100] Unless otherwise stated, all component or composition levels are in reference to the active portion of that component or composition, and are exclusive of impurities (e.g., residual solvents or by-products) that may be present in commercially available sources of such components or compositions.
[0101] shell
[0102] In order to produce the delivery particles of the present invention, an aqueous phase is prepared, which comprises one or more acids, chitosan and one or more redox initiators. The pH of the aqueous phase is adjusted to a pH of less than 6.5, or even to a pH range of 3 to 6.5. This treatment of chitosan produces a hydrolyzate that protonates the amine groups of at least a portion of the chitosan and promotes dissolution in water. The hydrolysis is carried out by heating for a period of time at an acidic pH, such as about 5 or 5.5 or 6. Optionally, a redox initiator can be added to the emulsion during the formation of the encapsulate, or a second redox initiator can be added to the emulsion alternatively. Adding persulfate to the aqueous phase and then adding peroxide to the emulsion achieves beneficial results. The first and second redox initiators can each be independently selected from persulfate or peroxide.
[0103] Modified chitosan (including redox initiator treated chitosan or acid treated and redox initiator treated chitosan) is used to react with a crosslinker (preferably isocyanate or polyisocyanate). This is achieved by preparing an oil phase, which contains the core material (including the beneficial agent) and the crosslinker that forms the shell. When the oil phase is combined with the aqueous phase under high shear stirring, an emulsion is formed. The emulsion is heated, for example to about 60 to 95°C, or even 60 to 80°C, or even 70 to 80°C, to initiate the reaction with the oil phase crosslinker (e.g., isocyanate). As the reaction proceeds, a redox initiator may optionally be added to the emulsion. The redox initiator may be the same as the first redox initiator added to the aqueous phase or may optionally be a second redox initiator.
[0104] The oil phase is prepared by dissolving an isocyanate such as a trimer of xylylene diisocyanate (XDI) or a polymer of methylene diphenyl isocyanate (MDI) in oil at 25°C. A diluent such as isopropyl myristate can be used to adjust the hydrophilicity of the oil phase. The oil phase is then added to the water phase and ground at high speed to obtain a target size. The emulsion is solidified in one or more heating steps, such as heating to 40°C in 30 minutes and keeping at 40°C for 60 minutes. The time and temperature are approx. 1000 rpm. The temperature and time are selected to be sufficient to form and solidify a shell at the interface of the oil phase droplets and the water continuous phase. For example, the emulsion is heated to 85°C in 60 minutes and then kept at 85°C for 360 minutes to solidify the capsule. The slurry is then cooled to room temperature.
[0105] A population of delivery particles according to the present disclosure may be characterized by a volume weighted median particle size of about 1 to about 100 microns, preferably about 10 to about 100 microns, preferably about 15 to about 50 microns, more preferably about 20 to about 40 microns, and even more preferably about 25 to about 35 microns. For some compositions, it may be preferred that the population of delivery particles be characterized by a volume weighted median particle size of about 1 to about 50 microns, preferably about 5 to about 20 microns, and more preferably about 10 to about 15 microns. Different particle sizes can be obtained by controlling the droplet size during emulsification.
[0106] The delivery particle may be characterized by a core to shell ratio of up to 99:1, or even 99.5:0.5 by weight. The shell may be present at a level of about 1% to about 25%, preferably about 1% to about 20%, preferably about 1% to 15%, more preferably about 5% to about 15%, even more preferably about 10% to about 15%, even more preferably about 10% to about 12%, by weight of the delivery particle. The shell may be present at a level of at least 1%, preferably at least 3%, more preferably at least 5%, by weight of the delivery particle. The shell may be present at a level of up to about 25%, preferably up to about 20%, preferably up to about 15%, more preferably up to about 12%, by weight of the delivery particle.
[0107] The delivery particles may be cationic in nature, preferably cationic at pH 4.5. The delivery particles may be characterized by a zeta potential of at least 15 millivolts (mV) at pH 4.5. The delivery particles may be made to have a zeta potential of at least 15 millivolts (mV) at pH 4.5, or even at least 40 mV at pH 4.5, or even at least 60 mV at pH 4.5. Delivery particles prepared with chitosan typically exhibit a positive zeta potential. Such capsules have improved deposition efficiency on fabrics. At higher pH, the particles may be able to be made nonionic or anionic.
[0108] For the purposes of the present invention, the crosslinking agents, preferably isocyanates or polyisocyanates, which can be used in the present invention are understood to be isocyanate monomers, isocyanate oligomers, isocyanate prepolymers, or dimers or trimers of aliphatic or aromatic isocyanates. All such monomers, prepolymers, oligomers, or dimers or trimers of aliphatic or aromatic isocyanates are intended to be included in the term "isocyanate" as used herein.
[0109] Cross-linking agent can include aliphatic or aromatic monomers, oligomers or prepolymers, and can have two or more isocyanate functional groups. Isocyanate can be selected from aromatic toluene diisocyanate and derivatives thereof (for delivery of the wall formation of particles), or aliphatic monomers, oligomers or prepolymers, such as hexamethylene diisocyanate and dimer or trimer thereof, or 3,3,5-trimethyl-5-isocyanatomethyl-1-isocyanatocyclohexane tetramethylene diisocyanate. Polyisocyanates can be selected from 1,3-diisocyanato-2-methylbenzene, hydrogenated MDI, bis(4-isocyanatocyclohexyl)methane, dicyclohexylmethane-4,4'-diisocyanate and their oligomers and prepolymers. This list is illustrative and is not intended to limit the polyisocyanates available in the present invention.
[0110] The isocyanates useful in the present invention may comprise isocyanate monomers, oligomers or prepolymers, or dimers or trimers thereof, having at least two isocyanate groups. Optimized crosslinking can be achieved with isocyanates having at least three functional groups.
[0111] For the purposes of the present invention, crosslinking agents are understood to include, by way of illustration and not limitation, any isocyanate monomer, oligomer, prepolymer or polymer having at least two isocyanate groups and containing aliphatic or aromatic moieties in the monomer, oligomer or prepolymer. If aromatic, the aromatic moiety may contain phenyl, toluoyl, xylyl, naphthyl or diphenyl moieties, more preferably toluoyl or xylyl moieties. Aromatic polyisocyanates are understood to be polyisocyanates containing at least one aromatic moiety. For the purposes of the present invention, aromatic polyisocyanates may include diisocyanate derivatives, such as biuret and polyisocyanurate. When aromatic, polyisocyanates may be, but are not limited to, methylene diphenyl diisocyanate, [diisocyanato (phenyl) methyl] benzene, toluene diisocyanate, tetramethyl dimethyl toluidine diisocyanate, polyisocyanurates of toluene diisocyanate (which may be referred to under the trade name RC is commercially available from Bayer), trimethylolpropane adduct of toluene diisocyanate (available under the trade name L75 is commercially available from Bayer), or a trimethylolpropane adduct of naphthalene-1,5-diisocyanate, phenylene diisocyanate, 2,2'-methylene diphenyl diisocyanate, 4,4'-methylene diphenyl diisocyanate, 2,4'-methylene diphenyl diisocyanate, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate, 1,4-phenylene diisocyanate, 1,3-diisocyanatobenzene, or xylylene diisocyanate (available under the trade name D-110N is commercially available from Mitsui Chemicals), and combinations thereof.
[0112] Aliphatic isocyanates are understood to be monomeric, oligomeric, prepolymeric or polymeric polyisocyanates that do not contain any aromatic moieties. Aromatic polyisocyanates are understood to be polyisocyanates that contain at least one aromatic moiety. Aromatic polyisocyanates are preferred, however, aliphatic polyisocyanates and blends thereof are useful. Aliphatic polyisocyanates include trimers of hexamethylene diisocyanate, trimers of isophorone diisocyanate, trimethylolpropane adducts of hexamethylene diisocyanate (available from Mitsui Chemicals) or biuret of hexamethylene diisocyanate (available under the trade name N 100 is commercially available from Bayer).
[0113] The capsule shell may also be reinforced using additional co-crosslinking agents such as multifunctional amines and / or polyamines, such as diethylenetriamine (DETA), polyethyleneimine and polyethyleneamine. For example, acrylates may also be used as additional co-crosslinking agents to reinforce the shell.
[0114] The polymer material may be formed in a reaction wherein the weight ratio of chitosan present in the reaction to the crosslinking agent present in the reaction is from about 1:10 to about 1:0.1. It is believed that selecting a desired ratio of biopolymer to crosslinking agent can provide desired ductility benefits as well as improved biodegradability. It may be preferred that at least 21% by weight of the shell is composed of moieties derived from chitosan, preferably derived from acid-treated chitosan. The chitosan may be from about 21% to about 95% of the shell as a percentage of the weight of the shell. The ratio of chitosan in the aqueous phase to the crosslinking agent, preferably an isocyanate, in the oil phase may be from 21:79 to 90:10, or even 1:2 to 9:1, or even 1:1 to 7:1, based on weight. The polymer material may be formed in a reaction wherein the weight ratio of chitosan or a derivative thereof (which may include acid-treated chitosan) present in the reaction to the crosslinking agent present in the reaction is from about 1:10 to about 10:1, preferably from about 1:5 to about 5:1, preferably from about 1:4 to about 5:1, more preferably from about 1:1 to about 5:1, more preferably from about 3:1 to about 5:1. The shell may comprise chitosan at a level of 21 wt% or even greater, preferably from about 21 wt% to about 90 wt%, or even 21 wt% to 85 wt%, or even 21 wt% to 75 wt%, or 21 wt% to 55 wt% of the total shell being chitosan. The chitosan of this paragraph is preferably a modified chitosan as described herein.
[0115] core
[0116] The delivery particles of the present invention include beneficial agents, which include one or more compositions intended to be encapsulated. Beneficial agents are preferably spices or fragrances, but can be selected from many different materials, such as chromogens and dyes, fragrances, spices, sweeteners, fragrances, oils, fats, pigments, cleaning oils, medicines, medicinal oils, perfume oils, mold inhibitors, antimicrobial agents, fungicides, bactericides, disinfectants, adhesives, phase change materials, odorants, fertilizers, nutrients and weed killers: as an illustration and not as a limitation. Beneficial agents and oils constitute the core. The core can be liquid or solid. For a core that is solid at ambient temperature, the wall material can be effectively wrapped less than the entire core for some applications, such as in applications, the availability of the desired agglomerate core. Such purposes can include odor release, cleaning compositions, emollients, cosmetic delivery, etc. When the encapsulant core is a phase change material, uses may include such encapsulants in mattresses, pillows, bedding, textiles, athletic equipment, medical devices, building products, construction products, HVAC, renewable energy, apparel, athletic surfaces, electronics, automotive, aviation, footwear, beauty care, laundry, and solar energy.
[0117] The core constitutes the material encapsulated by the microcapsule. Typically, particularly when the core material is a liquid material, the core material and the composition of the inner wall forming the microcapsule or one or more combinations of the solvent for the beneficial agent or the distribution modifier. If the core material can play the role of an oil solvent in the capsule, such as acting as a solvent or carrier of a wall-forming material or a beneficial agent, the core material can be made to become the main material to be encapsulated, or if the carrier itself is a beneficial agent, it can be the whole material to be encapsulated. However, often, the beneficial agent is 0.01-99 weight percent of the capsule internal content, preferably 0.01-about 65 weight % of the capsule internal content, and more preferably 0.1-about 45 weight % of the capsule internal content. For some applications, even if only trace amounts, the core material can also be effective.
[0118] When the benefit agent itself is not sufficient to act as an oil phase or solvent, particularly for wall-forming materials, the oil phase may comprise a suitable carrier and / or solvent. In this sense, the oil is optional, as the benefit agent itself may sometimes be an oil. These carriers or solvents are typically oils, preferably having a boiling point greater than about 80° C. and having low volatility and being non-flammable. Although not limited thereto, they preferably comprise one or more esters, preferably having a chain length of up to 18 carbon atoms or even up to 42 carbon atoms and / or triglycerides such as esters of C6-C12 fatty acids and glycerol. Exemplary carriers and solvents include, but are not limited to, ethyl diphenylmethane; isopropyl diphenylethane; butyl diphenylethane; benzyl xylene; alkyl biphenyls, such as propyl biphenyl and butyl biphenyl; dialkyl phthalates, such as dibutyl phthalate, dioctyl phthalate, dinonyl phthalate, and ditridecyl phthalate; 2,2,4-trimethyl-1,3-pentanediol diisobutyrate; alkyl benzenes, such as dodecylbenzene; alkyl or aralkyl benzoates, such as benzyl benzoate; diaryl ethers; di(aralkyl) ethers and aryl aralkyl ethers; ethers, such as diphenyl ether , dibenzyl ether and phenylbenzyl ether; liquid higher alkyl ketones (having at least 9 carbon atoms); alkyl or aralkyl benzoates, such as benzyl benzoate; alkylated naphthalenes, such as dipropylnaphthalene; partially hydrogenated terphenyls; high boiling point straight or branched chain hydrocarbons; alkylaryl hydrocarbons, such as toluene; vegetable oils and other crop oils, such as rapeseed oil, soybean oil, corn oil, sunflower oil, cottonseed oil, lemon oil, olive oil and pine oil; methyl esters of fatty acids derived from the transesterification of vegetable oils and other crop oils, methyl esters of oleic acid, esters of vegetable oils, such as soybean methyl esters, straight chain paraffin aliphatic hydrocarbons and mixtures of the foregoing.
[0119] Useful benefit agents include fragrance raw materials such as alcohols, ketones, aldehydes, esters, ethers, nitriles, olefins, fragrances, fragrance solubilizers, essential oils, phase change materials, lubricants, colorants, coolants, preservatives, antimicrobial or antifungal actives, herbicides, antiviral actives, preservative actives, antioxidants, bioactives, deodorants, emollients, moisturizers, exfoliants, UV absorbers, self-repairing compositions, corrosion inhibitors, sunscreens, silicone oils, waxes, hydrocarbons, higher fatty acids, essential oils, lipids, skin coolants, vitamins, sunscreens, antioxidants, glycerin, catalysts, bleaching particles, silica particles, odor reducing agents, dyes, whitening agents, antibacterial actives, antiperspirant actives, cationic polymers, and mixtures thereof. By way of illustration and not limitation, phase change materials useful as beneficial agents may include alkanes having 13-28 carbon atoms, various hydrocarbons such as n-octacosane, n-heptacosane, n-hexacosane, n-pentacosane, n-tetracosane, n-tricosane, n-docosane, n-heneicosane, n-eicosane, n-nonadecane, octadecane, n-heptadecane, n-hexadecane, n-pentadecane, n-tetradecane, n-tridecane. The phase change material may alternatively optionally further include crystalline materials such as 2,2-dimethyl-1,3-propanediol, 2-hydroxymethyl-2-methyl-1,3-propanediol, acids of linear or branched hydrocarbons such as eicosanoic acid and esters such as methyl palmitate, fatty alcohols, and mixtures thereof.
[0120] Preferably, in the case of a fragrance, the fragrance oil acts as a solvent for the benefit agent and the wall forming material, as illustrated in the Examples herein.
[0121] Optionally, the aqueous phase may include an emulsifier. Non-limiting examples of emulsifiers include the following water-soluble salts: alkyl sulfates, alkyl ether sulfates, alkyl isothionates, alkyl carboxylates, alkyl sulfosuccinates, alkyl succinamates, alkyl sulfates such as sodium lauryl sulfate, alkyl sarcosinates, alkyl derivatives of protein hydrolysates, acyl aspartates, alkyl or alkyl ether or alkyl aryl ether phosphates, sodium lauryl sulfate, phospholipids or lecithin, or stearic acid soaps, sodium stearate, potassium stearate or ammonium stearate, oleate or palmitate, alkyl aryl sulfonates such as sodium dodecylbenzene sulfonate, dialkyl sodium sulfosuccinate, dioctyl sodium sulfosuccinate, dilauryl sodium sulfosuccinate, poly(styrene sulfonate) sodium salt, isobutylene-maleic anhydride copolymer, gum arabic, sodium alginate, carboxymethyl cellulose, cellulose sulfate and pectin, poly(styrene sulfonate), isobutylene-maleic anhydride copolymer, carrageenan, sodium alginate, pectic acid, tragacanth gum, almond gum and agar; semisynthetic polymers such as carboxymethyl cellulose, sulfated cellulose, sulfated methyl cellulose, carboxymethyl starch, phosphorylated starch, lignin sulfonic acid; and synthetic polymers such as maleic anhydride copolymers (including hydrolyzates thereof), polyacrylic acid, polymethacrylic acid, butyl acrylate copolymers or crotonic acid homopolymers and copolymers, vinylbenzenesulfonic acid or 2-acrylamido-2-methylpropanesulfonic acid homopolymers and copolymers, and partial amides or partial esters of these polymers and copolymers, carboxyl-modified polyvinyl alcohol, sulfonic acid-modified polyvinyl alcohol and phosphoric acid-modified polyvinyl alcohol, phosphorylated or sulfated tristyrylphenol ethoxylates, palmitamidopropyltrimonium chloride (VarisoftPATC TM, available from Degussa Evonik, Essen, Germany), distearyl diammonium chloride, cetyltrimethylammonium chloride, quaternary ammonium compounds, fatty amines, aliphatic ammonium halides, alkyldimethylbenzylammonium halides, alkyldimethylethylammonium halides, polyethyleneimine, poly(2-dimethylaminoethyl methacrylate) methyl chloride quaternary salt, poly(l-vinylpyrrolidone-co-2-dimethylaminoethyl methacrylate), poly(acrylamide-co-diallyldimethylammonium chloride), poly(allylamine), quaternized poly[bis(2-chloroethyl)ether-alt-1,3-bis[3-(dimethylamino)propyl]urea] and poly(dimethylamine-co-epichlorohydrin-co-ethylenediamine), condensation products of aliphatic amines with alkylene oxides, quaternary poly(s) having long-chain aliphatic groups Ammonium compounds, such as distearyl diammonium chloride, and fatty amines, alkyl dimethyl benzyl ammonium halides, alkyl dimethyl ethyl ammonium halides, polyalkylene glycol ethers, condensation products of alkyl phenols, aliphatic alcohols or fatty acids with alkylene oxides, ethoxylated alkyl phenols, ethoxylated aryl phenols, ethoxylated polyaryl phenols, carboxylates solubilized with polyols, polyvinyl alcohol, polyvinyl acetate, or copolymers of polyvinyl alcohol polyvinyl acetate, polyacrylamide, poly(N-isopropylacrylamide), poly(2-hydroxypropyl methacrylate), poly(-ethyl-2-oxazoline), poly(2-isopropenyl-2-oxazoline-co-methyl methacrylate), poly(methyl vinyl ether), and polyvinyl alcohol-co-ethylene), and cocamidopropyl betaine. Emulsifiers, if used, are typically present in an amount of about 0.1-40% by weight, preferably 0.2 to about 15% by weight, more typically 0.5 to 10% by weight, based on the total weight of the formulation.
[0122] In addition to the beneficial agent, the delivery particle may also encapsulate a partitioning modifier. Non-limiting examples of partitioning modifiers include isopropyl myristate, C4-C 24 Monoesters, diesters and triesters of fatty acids, castor oil, mineral oil, soybean oil, hexadecanoic acid, methyl ester isododecane, isoparaffin oil, polydimethylsiloxane, brominated vegetable oil and combinations thereof. The delivery particles can also have different ratios of distribution modifiers and beneficial agents to prepare different delivery particle populations that can have different bloom patterns. Such a population can also incorporate different perfume oils to prepare delivery particle populations that display different bloom patterns and different odor experiences. Patent publication US 2011-0268802 discloses other non-limiting examples of delivery particles and distribution modifiers and is incorporated herein by reference.
[0123] Optionally, if desired, the delivery particles can be dehydrated, for example by decantation, filtration, centrifugation or other separation techniques. Alternatively, the aqueous slurry delivery particles can be spray dried.
[0124] In some examples of the method and composition, the delivery particles may be composed of one or more different groups. The composition may have at least two different delivery particle groups, which are different in terms of the exact composition of the fragrance oil and the median particle size and / or the distribution modifier and fragrance oil (PM:PO) weight ratio. In some examples, the composition includes more than two different groups, which are different in terms of the exact composition of the fragrance oil and its burst strength. In some other examples, the delivery particle group may be different in terms of the weight ratio of the distribution modifier and one or more fragrance oils. In some examples, the composition may include a first delivery particle group with a first ratio and a second delivery particle group with a second ratio, the first ratio being 2:3 to 3:2 for the weight ratio of the distribution modifier and the first fragrance oil, and the second ratio being less than 2:3 but greater than 0 for the weight ratio of the distribution modifier and the second fragrance oil.
[0125] In some embodiments, each different delivery particle population can be prepared in a different slurry. For example, a first delivery particle population can be included in a first slurry and a second delivery particle population can be included in a second slurry. It is understood that there is no limit to the number of different slurries used in combination, and the formulator's choice allows for the combination of 3, 10, or 15 different slurries. The first and second delivery particle populations can differ in the exact composition of the benefit agent (e.g., fragrance oil) and in the median particle size and / or PM:PO weight ratio.
[0126] In some embodiments, the composition can be prepared by combining the first and second slurries with at least one auxiliary component, and optionally packaged in a container. In some instances, the first and second delivery particle groups can be prepared in different slurries, and then spray-dried to form particulate matter. Different slurries can be combined before spray drying, or spray-dried separately and then combined together when in the form of a particulate powder. Once in powder form, the first and second delivery particle groups can be combined with auxiliary components to form a composition that can be used as a raw material for manufacturing consumer goods, industrial products, medical products or other commodities. In some instances, at least one delivery particle group is spray-dried and combined with a slurry of the second delivery particle group. In some instances, at least one delivery particle group is dried and prepared by spray drying, fluidized bed drying, tray drying or other such drying methods available.
[0127] In some examples, the slurry or dry particulate matter may include one or more auxiliary materials, such as processing aids selected from the following: carriers, aggregation-inhibiting materials, deposition aids, particle suspension polymers, and mixtures thereof. Non-limiting examples of aggregation-inhibiting materials include salts that can have a charge shielding effect around the particles, such as magnesium chloride, calcium chloride, magnesium bromide, magnesium sulfate, and mixtures thereof. Non-limiting examples of particle suspension polymers include polymers such as xanthan gum, carrageenan, guar gum, shellac, alginates / esters, chitosan; cellulosic materials such as carboxymethyl cellulose, hydroxypropyl methylcellulose, cationically charged cellulosic materials; polyacrylic acid; polyvinyl alcohol; hydrogenated castor oil; ethylene glycol distearate; and mixtures thereof.
[0128] In some embodiments, the slurry may include one or more processing aids selected from water, aggregation inhibiting materials such as divalent salts; particle suspending polymers such as xanthan gum, guar gum, carboxymethyl cellulose.
[0129] In other examples of the present invention, the slurry may include one or more carriers selected from the following: polar solvents, including but not limited to water, ethylene glycol, propylene glycol, polyethylene glycol, glycerin; non-polar solvents, including but not limited to mineral oil, fragrance raw materials, silicone oil, hydrocarbon paraffin oil, and mixtures thereof.
[0130] In some examples, the slurry may include a deposition aid, which may include a polymer selected from the group consisting of: polysaccharides, in one aspect, cationically modified starch and / or cationically modified guar gum; polysiloxanes; polydiallyldimethylammonium halides; copolymers of polydiallyldimethylammonium chloride and polyvinyl pyrrolidone; compositions comprising polyethylene glycol and polyvinyl pyrrolidone; acrylamide; imidazole; imidazolinium halides; polyvinylamine; copolymers of polyvinylamine and N-vinyl formamide; polyvinyl formamide, polyvinyl alcohol; polyvinyl alcohol cross-linked with boric acid; polyacrylic acid; polyglyceryl ether silicone cross-polymers; copolymers of polyacrylic acid, polyacrylate, polyvinylamine and polyvinyl alcohol; low molecular weight amines; Polymers, in one aspect diethylenetriamine, ethylenediamine, bis(3-aminopropyl)piperazine, N,N-bis-(3-aminopropyl)methylamine, tris(2-aminoethyl)amine and mixtures thereof; polyethyleneimine, derivatized polyethyleneimine, in one aspect ethoxylated polyethyleneimine; polymer compounds comprising at least two moieties selected from the group consisting of carboxylic acid moieties, amine moieties, hydroxyl moieties and nitrile moieties on the backbone of polybutadiene, polyisoprene, polybutadiene / styrene, polybutadiene / acrylonitrile, carboxyl-terminated polybutadiene / acrylonitrile or combinations thereof; preformed coacervates of anionic surfactants in combination with cationic polymers; polyamines and mixtures thereof.
[0131] In some additional examples illustrating the present invention, at least one population of delivery particles may be contained in an agglomerate and then combined with a different population of delivery particles and at least one auxiliary material. The agglomerate may include a material selected from the group consisting of silicon dioxide, citric acid, sodium carbonate, sodium sulfate, sodium chloride, and a binder such as sodium silicate, modified cellulose, polyethylene glycol, polyacrylate, polyacrylic acid, zeolite, and mixtures thereof.
[0132] Suitable equipment for use in the methods disclosed herein may include continuous stirred tank reactors, homogenizers, turbine agitators, recirculation pumps, paddle mixers, plow shear mixers, ribbon blenders, longitudinal axis granulators and drum mixers (both in batch and (when applicable) continuous process configurations), spray dryers and extruders. Such equipment can be obtained from Lodige GmbH (Paderborn, Germany), Littleford Day, Inc. (Florence, Kentucky, USA), Forberg AS (Larvik, Norway), Glatt Ingenieurtechnik GmbH (Weimar, Germany), Niro (Soeborg, Denmark), Hosokawa Bepex Corp. (Minneapolis, Minnesota, USA), Arde Barinco (New Jersey, USA).
[0133] Test Method
[0134] It is understood that the test methods disclosed in the Test Methods section of this application should be used to determine the various values of the parameters of applicant's claimed subject matter as claimed and described herein.
[0135] Determination of molecular weight and related parameters of polymers
[0136] The following method describes gel permeation chromatography with multi-angle light scatterer and refractive index detection (GPC-MALS / RI) used to study molecular weight distribution measurements and related values for the polymers described herein.
[0137] Gel Permeation Chromatography (GPC) with Multi-angle Light Scattering (MALS) and Refractive Index (RI) detection (GPC-MALS / RI) allows the absolute molecular weight of polymers to be measured without the need for column calibration methods or standards. The GPC system allows molecules to be separated according to their molecular size. MALS and RI allow information on number average (Mn) and weight average (Mw) molecular weights to be obtained.
[0138] The Mw distribution of water-soluble polymers such as chitosan is typically measured by using a liquid chromatography system (e.g., Agilent 1260 Infinity pump system using OpenLab Chemstation software, Agilent Technology, Santa Clara, CA, USA) and a column set (e.g., 2 Tosoh TSKgel G6000WP 7.8×300mm 13um pore size, guard column A0022 6mm×40mm PW xl-cp, King of Prussia, PA) operating at 40°C. The mobile phase is 0.1 M sodium nitrate in water containing 0.02% sodium azide and 0.2% acetic acid. The mobile phase solvent is pumped isocratically at a flow rate of 1 mL / min. The column was prepared using a Wyatt Multi-angle light scattering (18-angle MALS) detector controlled by software v8.0 and a differential refractive index (RI) detector (Wyatt Technology of Santa Barbara, California, USA).
[0139] Samples were typically prepared at room temperature by dissolving chitosan material at ~1 mg / ml in the mobile phase and hydrated by mixing the solution overnight. Samples were filtered through a 0.8 μm Versapor membrane filter (PALL, Life Sciences, New York, USA) using a 3-ml syringe into an LC autosampler vial prior to GPC analysis.
[0140] The dn / dc value (differential change of refractive index with concentration, 0.15) was used for number average molecular weight (Mn), weight average molecular weight (Mw), Z average molecular weight (Mz), peak maximum molecular weight (Mp) and polydispersity (Mw / Mn) determinations by the Astra detector software.
[0141] Figure 1 An illustrative example of these points on a hypothetical graph of the molecular weight distribution of a polymer is shown in , where: Mn is indicated by structure number 1; Mp is indicated by structure number 2; Mw is indicated by structure number 3; and Mz is indicated by structure number 4.
[0142] Viscosity
[0143] The viscosity of the liquid finished product was measured using an AR 550 rheometer / viscometer from TA instruments (New Castle, DE, USA) using parallel steel plates with a diameter of 40 mm and a gap size of 500 μm. The viscosity of the liquid finished product was measured from 0.01 s to 100 s at 21 °C within 3 minutes.-1 Up to 25s -1 The logarithmic shear rate scan was acquired for 20 s -1 High shear viscosity and 0.05s -1 Low shear viscosity.
[0144] Test Methods for Determining logP
[0145] The log value of the octanol / water partition coefficient (logP) is calculated for each material tested (e.g., each PRM in a fragrance mixture). The logP of individual materials (e.g., PRMs) is calculated using the Consensus logP calculation model, version 14.02 (Linux), available from Advanced Chemistry Development Inc. (ACD / Labs) (Toronto, Canada) to provide dimensionless logP values. The Consensus logP calculation model from ACD / Labs is part of the ACD / Labs model suite.
[0146] Volume-weighted particle size and size distribution
[0147] Volume weighted particle size distribution was determined via single particle optical sensing (SPOS) (also known as optical particle counting (OPC)) using an AccuSizer 780 AD instrument and accompanying software CW788 version 1.82 (Particle Sizing Systems, Santa Barbara, California, USA) or equivalent. The instrument was configured to the following conditions and options: flow rate = 1 ml / sec; lower size threshold = 0.50 μm; sensor model = sensor model = LE400-05 or equivalent; automatic dilution = on; collection time = 60 seconds; number of channels = 512; container flow volume = 50 ml; maximum consistency = 9200. The measurement was started by placing the sensor in a cold state by flushing with water until the background count was less than 100. The delivery capsule sample in the suspension was introduced and the density of its capsule was adjusted with DI water via automatic dilution, if necessary, to produce a capsule count of at least 9200 / ml. The suspension was analyzed during a time period of 60 seconds. The resulting volume-weighted PSD data is plotted and recorded, and the desired volume-weighted particle size value (eg, median / 50th percentile, 5th percentile, and / or 90th percentile) is determined.
[0148] Procedure for determining % degradation
[0149] The % degradation was determined by the "OECD Guideline for Testing Chemicals" 301B CO2 Emission (Modified Sturm Test), adopted on July 17, 1992. For ease of reference, this test method is referred to herein as Test Method OECD 301B.
[0150] Procedure for determination of free oil
[0151] This method measures the amount of oil in the aqueous phase and uses 1 mg / ml dibutyl phthalate (DBP) / hexane as an internal standard solution.
[0152] Slightly more than 250 mg of DBP was weighed into a small beaker and transferred to a 250 ml container. Rinse the beaker thoroughly. Fill to 250 ml with hexane.
[0153] Sample preparation: About 1.5-2 grams (40 drops) of capsule slurry was weighed into a 20 ml scintillation vial and 10 ml of ISTD solution was added and the cap was tightly closed. After vigorous shaking several times within 30 minutes, the solution was pipetted into an autosampler vial and analyzed by GC.
[0154] Additional details. Instrument: HP5890 GC connected to HP Chem Station software; Column: 5m x 0.32 mm id with 1 μm DB-1 liquid phase; Temperature 50°C; hold for 1 minute then heat to 320°C; at 15 degrees / min; Injector: 275°C; Detector: 325°C; 2 ul injection.
[0155] Calculation: For both samples and calibration, add the total peak areas minus the area of DBP.
[0156] i) Calculate mg of free core oil:
[0157]
[0158] ii) Calculate free core oil %
[0159]
[0160] Procedure for Beneficial Agent Leakage Determination
[0161] Obtain 2 one gram samples of the benefit agent granule composition. Add 1 gram (Sample 1) of the granule composition to 99 grams of the product base (where the granules will be used). Age the product base (Sample 1) containing the granules at 35°C in a sealed glass jar for 2 weeks. Similarly age another one gram sample (Sample 2).
[0162] After 2 weeks, filtration was used to recover particles of the granular composition from the product matrix (Sample 1) and from the granular composition (Sample 2). Each granular sample was treated with a solvent that would extract all of the beneficial agent from each sample particle. The solvent containing the beneficial agent from each sample was injected into a gas chromatograph and the peak areas were integrated to determine the total amount of beneficial agent extracted from each sample.
[0163] The beneficial agent leakage percentage is determined by calculating the difference obtained by subtracting the total amount of beneficial agent extracted from Sample 1 from the total amount of beneficial agent extracted from Sample 2, expressed as a percentage of the total amount of beneficial agent extracted from Sample 2, as shown in the following formula:
[0164]
[0165] Delivery particles can be prepared that exhibit a positive zeta potential. Such capsules have improved deposition efficiency, for example, on fabrics.
[0166] Sample preparation for biodegradability measurements
[0167] Water-soluble or water-dispersible materials were purified via crystallization until greater than 95% purity was achieved and dried prior to biodegradability measurements.
[0168] The oily medium containing the beneficial agent needs to be extracted from the delivery particle slurry in order to analyze only the polymer wall. Therefore, the delivery particle slurry is freeze-dried to obtain a powder. Then, it is further washed with an organic solvent via Soxhlet extraction to extract the oily medium containing the beneficial agent until the weight percentage of the oily medium based on the total delivery particle polymer wall is less than 5%. Finally, the polymer wall is dried and analyzed.
[0169] The weight ratio of delivery particles to solvent was 1:3. The residual oily medium was determined by thermogravimetric analysis (isothermal at 100°C for 60 minutes and at 250°C for another 60 minutes). The measured weight loss needed to be less than 5%.
[0170] OECD 301B – Biodegradability Method
[0171] Within 60 days in accordance with the guidelines of the Organisation for Economic Co-operation and Development (OECD) - OECD (1992), Test No. 301: Ready Biodegradability, OECD Guidelines for Testing Chemicals, Part 3, OECD Publishing, Paris, https: / / doi.org / 10.1787 / 9789264070349-en To measure the cumulative CO2 release.
[0172] leakage
[0173] The amount of beneficial agent leakage from the beneficial agent-containing delivery particles was determined according to the following method:
[0174] i) Two 1 g samples of the stock slurry of delivery particles containing the benefit agent were obtained.
[0175] ii) 1 g of the raw slurry of the delivery particles containing the benefit agent was added to 99 g of the consumer product base (where the particles were to be used) and the mixture was labeled Sample 1. A second 1 g sample of the raw particle slurry was used immediately in step d below in its pure form without contact with the consumer product base and was labeled Sample 2.
[0176] iii) The product matrix containing the delivery particles (Sample 1) was aged at 35°C in a sealed glass jar for 1 week.
[0177] iv) Particles were recovered from both samples using filtration. Particles in Sample 1 (in the consumer product matrix) were recovered after the aging step. Particles in Sample 2 (pure feedstock slurry) were recovered at the same time as the Sample 1 aging step was initiated.
[0178] v) treating the recovered particles with a solvent to extract the benefit agent material from the particles.
[0179] vi) analyzing via chromatography the solvent containing the beneficial agent extracted from each sample.
[0180] vii) The resulting benefit agent peak areas under the curves were integrated and the areas summed to determine the total amount of benefit agent extracted from each sample.
[0181] viii) The percentage of beneficial agent leakage is determined by calculating the difference obtained by subtracting the total amount of beneficial agent extracted from Sample 1 (S1) from the total amount of beneficial agent extracted from Sample 2 (S2), expressed as a percentage of the total amount of beneficial agent extracted from Sample 2 (S2), as shown in the following formula:
[0182]
[0183] Volume weighted median particle size
[0184] Particle size is measured using a static light scattering device such as an Accusizer 780A (manufactured by ParticleSizing Systems, Santa Barbara, California). The instrument is calibrated from 0 to 300μ using Duke particle size standards. Samples for particle size evaluation are prepared by diluting about 1 g of the emulsion if the volume weighted median particle size of the emulsion is to be determined, or 1 g of the delivery particle slurry containing the benefit agent if the volume weighted median particle size of the finished particles is to be determined, in about 5 g of deionized water, and further diluting about 1 g of this solution in about 25 g of water.
[0185] Add approximately 1 g of the maximum diluted sample to the Accusizer and start the test using the auto-dilution feature. The Accusizer should read over 9200 counts / second. If the count is less than 9200, additional sample should be added. The Accusizer will dilute the test sample until 9200 counts / second and begin evaluation. After 2 minutes of testing, the Accusizer will display the results, including the volume-weighted median size.
[0186] The breadth index can be calculated by determining the particle size that accounts for more than 95% of the cumulative particle volume (95% size), the particle size that accounts for more than 5% of the cumulative particle volume (5% size), and the median particle size (50% size - 50% of the particle volume is above this size and 50% of the particle volume is below this size). Breadth index = ((95% size) - (5% size) / 50% size).
[0187] Unless otherwise indicated, all temperatures herein are in degrees Celsius (° C.) Unless otherwise indicated, all measurements herein are made at 20° C. and under atmospheric pressure.
[0188] Unless otherwise indicated, all percentages and ratios are calculated by weight. Unless otherwise indicated, all percentages and ratios are calculated based on the total composition.
[0189] It should be understood that each maximum numerical limit given throughout this specification includes each lower numerical limit, as if such lower numerical limits are explicitly written in this article. Each minimum numerical limit given throughout this specification will include each higher numerical limit, as if such higher numerical limits are explicitly written in this article. Each numerical range given throughout this specification will include each narrower numerical range that falls within such a wider numerical range, as if such a narrower numerical range is explicitly written in this article.
[0190] Procedure for measuring the compatibility of delivery particles in laundry matrices
[0191] The compatibility of delivery particles in laundry matrix is measured by the percentage of aggregates formed in the laundry agent matrix. Use an overhead mixer to stir for at least one minute to homogenize the slurry containing delivery particles. Then, under mixing, the homogenized slurry is added to the laundry matrix, such as a single unit dose (SUD) matrix, at a ratio of 1:40 (e.g., 1g slurry in 40g matrix). Use an overhead mixer to mix the above mixture at 350rpm for at least 15 minutes. Then, the mixture of delivery particles and laundry matrix is poured through a 425 μm sieve after mixing. Particle aggregates are washed with a large amount of deionized (DI) water on the sieve until no visible laundry matrix is observed. Collect the original and water washing filtrate and then pass through a 212um sieve to collect any particle aggregates on the 212um sieve. Then, a large amount of DI water is used to wash the particle aggregates until no visible matrix is observed. The particle aggregates from the 212um and 425um sieves are merged and washed again with DI water to rinse off any remaining matrix. The particle aggregates were then collected and dried in a CEM oven to constant weight to determine the weight of particle aggregates in the laundry matrix. The percent aggregation was calculated by:
[0192]
[0193] EDX Method
[0194] Energy dispersive X-ray (EDX) microanalysis is an X-ray technique used to identify the elemental composition of a material. The technique can be qualitative or quantitative, and can even provide the spatial distribution of elements through mapping, as element concentrations can be collected from points, along lines, or as a map.
[0195] The instrument used in the methods as described herein was a scanning electron microscope (SEM) ZEISS 300 equipped with a Bruker Quantax 400 EDX detector.
[0196] To analyze the delivered particles in the premix or slurry, 2 μl of the slurry solution was deposited on a SEM stub (sample holder) that had been previously cleaned with acetone and then alcohol.
[0197] To analyze the delivery particles in the product composition, the particles can be extracted according to the "Extracting Delivery Particles from Finished Product" method provided below.
[0198] Use the EDX detector according to the manufacturer's instructions to collect the required data, using the guidance given below for qualitative and quantitative analysis.
[0199] The data generated by EDX analysis include spectra reported in a graph, where the x-axis is related to the reported X-ray energy (keV) and the y-axis is related to the signal intensity. The graph is characterized by different peaks, each corresponding to the characteristic energy of the detected element, which can then define the chemical composition of the analyzed sample.
[0200] A. Qualitative analysis
[0201] For a given sample, element mapping was performed to identify the surface arrangement of the detection elements obtaining an area of 140×95 um (corresponding to a magnification of 800X) using a resolution of 600×400 pixels for 3 minutes.
[0202] The chemical information generated by EDX technology can be visualized in several ways, including elemental mapping. For a specific region of interest (ROI), a digital image can be obtained in which the intensity of each location (pixel) is proportional to the intensity of each peak. Figure 1 A digital image of a specific ROI of a sample of a slurry of delivery particles is shown; a number of delivery particles 100 are shown. Figure 2 Displays various images (originally in color) associated with the intensity of each peak. Typically, the images are in color, with brighter colors associated with greater peak intensities. Figure 2 , first image 110 shows a representative sample of delivery particles 100. Second image 111 shows an image indicating the presence of carbon. Third image 112 shows an image indicating the presence of oxygen. Fourth image 113 shows an image indicating the presence of nitrogen. Fifth image 114 shows an image indicating the presence of sulfur. Sixth image 115 shows an image indicating the presence of chlorine.
[0203] B. Quantitative Analysis
[0204] The EDX technique can be used to detect the presence of elements, as well as their concentrations. The MDL (minimum detection limit) of this analytical technique is about 0.1 wt% for quantified elements; if the mass concentration is below the MDL, the element is not quantified.
[0205] For quantitative analysis, EDX spectra were acquired in an area of 50um x 40um for 3 minutes. The output is a spectrum with peaks identified as corresponding to the detected elements; a table showing the mass percentage and atomic distribution percentage (stoichiometric ratio) is also generated. Figure 3 A picture showing the spectrum for a given sample.
[0206] Extraction of delivery particles from finished product
[0207] Unless otherwise specified herein, the preferred method for separating delivery particles from the finished product is based on the fact that the density of most such delivery particles is different from the density of water. The finished product is mixed with water to dilute and / or release the delivery particles. The diluted product suspension is centrifuged to accelerate the separation of the delivery particles. Such delivery particles tend to float or sink in the diluted solution / dispersion of the finished product. Using a pipette or a spatula, the top and bottom layers of the suspension are removed and subjected to additional rounds of dilution and centrifugation to separate and enrich the delivery particles. Using an optical microscope equipped with crossed polarization filters or differential interference contrast (DIC), the delivery particles are observed at a total magnification of 100x and 400x. Microscopic observation provides an initial indication of the presence, size, quality and aggregation of the delivery particles.
[0208] To extract the delivery particles from the finished liquid fabric enhancer, the following procedure was performed:
[0209] 1. Place three equal portions of approximately 20 ml of liquid fabric enhancer into three separate 50 ml centrifuge tubes and dilute each portion 1:1 with DI water (e.g. 20 ml fabric enhancer + 20 ml DI water), mix each portion thoroughly, and centrifuge each portion at approximately 10,000×g for 30 minutes.
[0210] 2. After centrifugation according to step 1, discard the bottom water layer (about 10 ml) in each 50 ml centrifuge tube, and then add 10 ml of DI water to each 50 ml centrifuge tube.
[0211] 3. For each aliquot, repeat the centrifugation process, remove the bottom aqueous layer, and then add 10 ml of DI water to each 50 ml centrifuge tube two additional times.
[0212] 4. Remove the top layer with a spatula or pipette, and
[0213] 5. Transfer the top layer to a 1.8 ml centrifuge tube and centrifuge at approximately 20,000 x g for 5 minutes.
[0214] 6. Remove the top layer with a scraper and transfer to a new 1.8 ml centrifuge tube and add DI water until the tube is completely full, then centrifuge at approximately 20,000 × g for 5 minutes.
[0215] 7. Remove the bottom layer with a fine pipette and add DI water until the tube is completely full and centrifuge at approximately 20,000 x g for 5 minutes.
[0216] 8. Repeat step 7 5 more times (6 times total).
[0217] If both the top layer and bottom layer of the enriched delivery particles appear in step 1 above, move immediately to step 3 (i.e., omit step 2) and proceed to steps 4 to 8. Once these steps are completed, also remove the bottom layer from the 50 ml centrifuge tube of step 1 using a scraper or / and a pipette. Transfer the bottom layer to a 1.8 ml centrifuge tube and centrifuge at approximately 20,000 × g for 5 minutes. Remove the bottom layer in the new tube and add DI water until the tube is completely full, then centrifuge at approximately 20,000 × g for 5 minutes. Remove the top layer (water) and add DI water again until the tube is full. Repeat this another 5 times (6 times in total). Recombine the top and bottom layers enriched and separated for delivery particles.
[0218] If the fabric enhancer appears white or the delivery particle rich layer is difficult to distinguish, add 4 drops of dye (eg, Liquitint Blue JH 5% premix from Milliken & Company, Spartanburg, SC, USA) to the centrifuge tube from step 1 and separate as described.
[0219] To extract delivery particles from solid finished products that are easily dispersed in water, 1 L of DI water is mixed with 20 g of the finished product (e.g., detergent foams, films, gels, and granules; or water-soluble polymers; soap flakes and bars; and other readily water-soluble matrices, such as salts, sugars, clays, and starches). When extracting delivery particles from finished products that are not easily dispersed in water (e.g., waxes, desiccant tablets, desiccant bars, and oily materials), it may be necessary to add detergent, stir, and / or slightly heat the product and diluent to release the delivery particles from the matrix. The use of organic solvents or drying of the delivery particles should be avoided during the extraction step, as these actions can damage the delivery particles at this stage.
[0220] To extract the delivery particles from a liquid finished product that is not a fabric softener or fabric enhancer (e.g., liquid laundry detergent, liquid dishwashing detergent, liquid hand soap, lotion, shampoo, conditioner, and hair dye), 20 ml of the finished product is mixed with 20 ml of DI water. If necessary, NaCl (e.g., 1 to 4 g NaCl) may be added to the diluted suspension to increase the density of the solution and promote the delivery particles to float to the top layer. If the product is white and it is difficult to distinguish the delivery particle layer formed during the centrifugation process, a water-soluble dye may be added to the diluent to provide visual contrast.
[0221] The water and product mixture is subjected to several consecutive rounds of centrifugation, including removal of the top and bottom layers, resuspension of these layers in new diluent, and then further centrifugation, separation and resuspension. Each round of centrifugation occurs in a tube with a volume of 1.5 to 50 ml, using a centrifugal force of up to 20,000 × g for a period of 5 to 30 minutes. Typically at least six rounds of centrifugation are required to extract and clean enough delivery particles for testing. For example, the initial round of centrifugation can be performed in a 50 ml tube with a spin of 10,000 × g for 30 minutes, followed by five rounds of centrifugation, wherein the material from the top and bottom layers is resuspended in fresh diluent in a 1.8 ml tube and spun at 20,000 × g for 5 minutes each round.
[0222] If delivery particles are observed microscopically in both the top and bottom layers, then after the final centrifugation step, the delivery particles from both layers are recombined to produce a single sample containing all the delivery particles extracted from the product. The extracted delivery particles should be analyzed as soon as possible, but they can be stored as a suspension in DI water for up to 14 days before analyzing them.
[0223] Those skilled in the art will recognize that various other protocols may be constructed to extract and isolate the delivery particles from the finished product, and will recognize that such methods need to be validated via comparison of measurements made, as measured before and after the delivery particles are added to and extracted from the finished product.
[0224] In the following examples, the abbreviations correspond to the materials listed in Table 1.
[0225] Table 1
[0226] Product Name Chemical name Company / City ChitoClear Chitosan Primex EHF, Siglufjordur, Iceland Takenate D-110N Polyisocyanate prepolymer Mitsui Chemicals America, Inc., Rye Brook, NY hydrochloric acid Avantor Performance Materials, LLC, Radnor, PA Formic acid Brenntag Great Lakes,LLC,Wauwatosa,WI Potassium Persulfate Avantor Performance Materials, LLC, Radnor, PA Isopropyl myristate Acme-Hardesty Co.,Bule Bell,PA Hydrogen Peroxide Avantor Performance Materials, LLC, Radnor, PA
[0227] Example
[0228] Comparative Example 1.
[0229] Comparative Example 1 is the same as Example 13 disclosed in US20210252469 A1. The aqueous phase was prepared by dispersing 20.66g ChitoClear in 439.00g water while mixing in a jacketed reactor. The pH of the aqueous phase was then adjusted to 4.9 using concentrated HCl under stirring. The aqueous phase temperature was then raised to 85°C within 60 minutes, and then kept at 85°C for a period of time to hydrolyze ChitoClear. The aqueous phase temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step. The oil phase was prepared by mixing 159.38g of spice oil and 23.91g of isopropyl myristate with 4.00g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion. The emulsion was heated to 40°C within 30 minutes and then kept for 60 minutes. The pH of the emulsion was then adjusted to 2.97 using hydrochloric acid. The emulsion was then heated to 85°C and maintained at this temperature for 6 hours while mixing. The % degradability according to OECD 301 B at 28 days was 64.26%.
[0230] Comparative Example 2.
[0231] Comparative Example 2 is the same as Example 10 disclosed in US20210252469 A1. The aqueous phase was prepared by dispersing 20.66g ChitoClear in 439.00g water while mixing in a jacketed reactor. The pH of the aqueous phase was then adjusted to 6.0 using concentrated HCl under stirring. The aqueous phase temperature was then raised to 85°C within 60 minutes, and then kept at 85°C for a period of time to hydrolyze ChitoClear. The aqueous phase temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step. The oil phase was prepared by mixing 159.38g of spice oil and 23.91g of isopropyl myristate with 4.00g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion. The emulsion was heated to 40°C within 30 minutes and held for 60 minutes. The emulsion was then heated to 85°C and maintained at that temperature for 6 hours while mixing. Delivery particles were obtained and the % degradability of the delivery particles according to OECD 301B at 28 days was 11.07%.
[0232] Table 2
[0233] Comparative Example Water pH 1 week leak Degradability % (28 days) 1 4.9 76.18% 64.26 2 6.0 17.45% 11.07
[0234] As can be seen in Table 2, the delivery particles obtained in Comparative Example 1 at a relatively lower pH (4.9) degraded more strongly in the OECD degradability test. However, these delivery particles suffered from relatively high leakage. The delivery particles prepared at a slightly higher pH (6) performed better in terms of leakage but suffered from relatively poorer performance in the degradability test. There is a need for delivery particles with low leakage. It is even more desirable to have delivery particles with relatively high degradability at the same time. It was difficult to understand before the present invention to achieve a balance of low leakage but high degradability. It is even more difficult to understand delivery particles with low leakage, high degradability and compatibility with laundry substrates.
[0235] Example 1.
[0236] A stock solution of acid and potassium persulfate treated chitosan was prepared as follows. A potassium persulfate solution was first prepared by dissolving 1.55 g of potassium persulfate in 3287.5 g of deionized water at 70°C. Then 154.89 g of Chitosan ChitoClear was dispersed in the potassium persulfate solution while mixing in a jacketed reactor. The pH of the chitosan dispersion was then adjusted to 4.30 using 68.37 g of concentrated HCl under stirring. The temperature of the chitosan solution was then increased to 85°C over 60 minutes and then maintained at 85°C for a period of time to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid and potassium persulfate treated chitosan solution. The pH of the chitosan solution was 5.1. The chitosan stock solution formed was used to prepare the capsules in Examples 1, 3, 5 and 7.
[0237] The aqueous phase was prepared by mixing 420.27 g of the above chitosan stock solution in a jacketed reactor. The oil phase was prepared by mixing 128.30 g of spices and 54.99 g of isopropyl myristate with 4.01 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 40° C. in 30 minutes and then maintained for another 60 minutes. The obtained emulsion was then heated to 90° C. in 60 minutes and maintained at this temperature for 8 hours while mixing, then cooled to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 11.71 microns.
[0238] Example 2.
[0239] A stock solution of acid and potassium persulfate treated chitosan was prepared as follows. A potassium persulfate solution was first prepared by dissolving 1.55 g of potassium persulfate ("KPS") in 3287.97 g of deionized water at 70°C. 154.90 g of ChitoClear Chitosan was then dispersed in the potassium persulfate solution while mixing in a jacketed reactor. The pH of the chitosan dispersion was then adjusted to 5.10 using 51.72 g of concentrated HCl under stirring. The temperature of the chitosan solution was then increased to 85°C over 60 minutes, and then maintained at 85°C for a period of time to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid and potassium persulfate treated chitosan solution. The pH of the chitosan solution was 5.93. The chitosan stock solution formed was used to prepare the capsules in Examples 2, 4, 6 and 8.
[0240] The aqueous phase was prepared by mixing 422.15 g of the above chitosan stock solution in a jacketed reactor. The oil phase was prepared by mixing 128.30 g of spices and 54.99 g of isopropyl myristate with 4.01 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 40° C. in 30 minutes and then maintained for another 60 minutes. The obtained emulsion was then heated to 90° C. in 60 minutes and maintained at this temperature for 8 hours while mixing, then cooled to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 17.64 microns.
[0241] Table 3
[0242]
[0243] As can be seen in Table 3, the delivery particles based on added persulfate exhibit degradability, but as can be seen in Example 2, leakage is also improved relative to Example 1 with a slight change in pH. Furthermore, Example 2, in addition to improving leakage relative to Example 1, also exhibits 39.81% degradability over 28 days. This illustrates that the addition of persulfate can achieve a surprising balance of properties by producing degradable capsules that also have relatively reduced leakage. The desired attributes in an encapsulate are one or more of low leakage or degradability or compatibility with a matrix (e.g., a laundry detergent environment). Example 2 illustrates low leakage and degradability. Example 1 illustrates degradability.
[0244] Example 3.
[0245] The aqueous phase was prepared by mixing 420.27 g of the chitosan stock solution from Example 1 in a jacketed reactor. The oil phase was prepared by mixing 146.63 g of the fragrance and 36.66 g of isopropyl myristate with 5.55 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 40° C. within 30 minutes and then maintained for another 60 minutes. The obtained emulsion was then heated to 90° C. within 60 minutes and maintained at this temperature for 8 hours while mixing, after which it was cooled down to 25° C. within 90 minutes. The volume weighted median particle size of the formed capsules was 13.32 microns.
[0246] Example 4.
[0247] The aqueous phase was prepared by mixing 422.15 g of the chitosan stock solution from Example 2 in a jacketed reactor. The oil phase was prepared by mixing 146.63 g of the fragrance and 36.66 g of isopropyl myristate with 5.55 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 40° C. within 30 minutes and then maintained for another 60 minutes. The obtained emulsion was then heated to 90° C. within 60 minutes and maintained at this temperature for 8 hours while mixing, and then cooled down to 25° C. within 90 minutes. The volume weighted median particle size of the formed capsules was 14.29 microns.
[0248] Table 4
[0249]
[0250] As can be seen in Table 4, the delivery particles based on the added persulfate showed one-week leakage values of 44.25% and 27.20%, respectively. Even more surprisingly, with the subtle adjustment of pH, the degradability % in these samples increased from 13.14% to 39.97%. The delivery particles according to the present invention consistently show surprising improvements in leakage or degradability or compatibility with the substrate. In a preferred embodiment, improvements are seen in one category of attributes (e.g., leakage or degradability). More desirably, improvements are seen in two categories (e.g., leakage and degradability), such as shown to be achievable by Example 4 or previously in Example 2. Most desirably, improvements are seen in all three categories of leakage, degradability and compatibility. For example, appropriate selections can be obtained from the embodiments illustrated in Table 8. The parameters of the present invention are surprisingly able to assemble high-performance encapsulates in terms of leakage or degradability or substrate compatibility.
[0251] Example 5.
[0252] The aqueous phase was prepared by mixing 420.27 g of the chitosan stock solution from Example 1 in a jacketed reactor. The oil phase was prepared by mixing 146.63 g of the fragrance and 36.66 g of isopropyl myristate with 2.49 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 40° C. within 30 minutes and then maintained for another 60 minutes. The obtained emulsion was then heated to 90° C. within 60 minutes and maintained at this temperature for 8 hours while mixing, after which it was cooled down to 25° C. within 90 minutes. The volume weighted median particle size of the formed capsules was 18.06 microns.
[0253] Example 6.
[0254] The aqueous phase was prepared by mixing 422.15 g of the chitosan stock solution from Example 2 in a jacketed reactor. The oil phase was prepared by mixing 146.63 g of the fragrance and 36.66 g of isopropyl myristate with 2.49 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 40° C. within 30 minutes and then maintained for another 60 minutes. The obtained emulsion was then heated to 90° C. within 60 minutes and maintained at this temperature for 8 hours while mixing, and then cooled down to 25° C. within 90 minutes. The volume weighted median particle size of the formed capsules was 11.85 microns.
[0255] Table 5
[0256]
[0257] Examples 5 and 6 illustrate the improved degradability in capsules according to the present invention. In addition to the improved degradability, a surprising reduction in leakage is noted as the pH is adjusted closer to pH 6. These examples reinforce the trend observed in the previous examples, namely that the present invention is able to provide improvements in more than one category of attributes, more particularly in the attributes of leakage, degradability and compatibility.
[0258] Example 7.
[0259] The aqueous phase was prepared by mixing 420.27 g of the chitosan stock solution from Example 1 in a jacketed reactor. The oil phase was prepared by mixing 164.96 g of the fragrance and 18.33 g of isopropyl myristate with 4.01 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 40° C. within 30 minutes and then maintained for another 60 minutes. The obtained emulsion was then heated to 90° C. within 60 minutes and maintained at this temperature for 8 hours while mixing, and then cooled down to 25° C. within 90 minutes. The volume weighted median particle size of the formed capsules was 20.54 microns.
[0260] Example 8.
[0261] The aqueous phase was prepared by mixing 422.15 g of the chitosan stock solution from Example 2 in a jacketed reactor. The oil phase was prepared by mixing 164.96 g of the fragrance and 18.33 g of isopropyl myristate with 4.01 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 40° C. within 30 minutes and then maintained for another 60 minutes. The obtained emulsion was then heated to 90° C. within 60 minutes and maintained at this temperature for 8 hours while mixing, and then cooled down to 25° C. within 90 minutes. The volume weighted median particle size of the formed capsules was 12.56 microns.
[0262] Table 6
[0263]
[0264] Examples 7 and 8 illustrate improved degradability in capsules according to the present invention. In addition to improved degradability, reduced leakage was noted as the pH was adjusted closer to pH 6. These examples reinforce the trend observed in the previous examples, namely that the present invention is able to provide improvements in more than one category (in the categories of leakage, degradability, and compatibility).
[0265] Example 9
[0266] A stock solution of chitosan treated with acid and potassium persulfate was prepared as follows. Potassium persulfate solution was first prepared by dissolving 1.56g of potassium persulfate in 3303.96g of deionized water at room temperature. Then 155.68g of chitosan ChitoClear was dispersed in the potassium persulfate solution and mixed in a jacketed reactor. The pH of the chitosan dispersion was then adjusted to 5.80 using 53.88g of concentrated HCl under stirring. The temperature of the chitosan solution was then increased to 85°C within 60 minutes, and then kept at 85°C for a period of time (e.g., 2 hours) to hydrolyze and depolymerize the chitosan. Then after the hydrolysis step, the temperature was reduced to 25°C within a period of 90 minutes to obtain a chitosan solution treated with acid and potassium persulfate. The pH of the chitosan solution was 5.97.
[0267] The aqueous phase was prepared by mixing 2101.81 g of the above chitosan stock solution in a jacketed reactor. The oil phase was prepared by mixing 716.14 g of spices and 179.05 g of isopropyl myristate with 19.58 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes. The emulsion was then heated to 85° C. in 60 minutes and maintained at this temperature for 6 hours while mixing, then cooled to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 15.69 microns.
[0268] Example 10
[0269] A stock solution of chitosan treated with acid and potassium persulfate was prepared as follows. Potassium persulfate solution was first prepared by dissolving 1.56g of potassium persulfate in 3303.96g of deionized water at room temperature. Then 155.68g of chitosan ChitoClear was dispersed in the potassium persulfate solution and mixed in a jacketed reactor. The pH of the chitosan dispersion was then adjusted to 5.81 using 52.68g of concentrated HCl under stirring. The temperature of the chitosan solution was then increased to 85°C within 60 minutes, and then kept at 85°C for a period of time (e.g., 2 hours) to hydrolyze and depolymerize the chitosan. Then after the hydrolysis step, the temperature was reduced to 25°C within a period of 90 minutes to obtain a chitosan solution treated with acid and potassium persulfate. The pH of the chitosan solution was 5.90.
[0270] The aqueous phase was prepared by mixing 2456.58 g of the above chitosan stock solution in a jacketed reactor. The oil phase was prepared by mixing 714.38 g of spices and 178.6 g of isopropyl myristate with 27.07 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes. The emulsion was then heated to 85° C. in 60 minutes and maintained at this temperature for 6 hours while mixing, then cooled to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 20.54 microns.
[0271] Table 7
[0272]
[0273] Examples 9 and 10 illustrate improvements in multiple property categories in improved degradability and improved leakage values (lower the better) in capsules according to the present invention. In addition to improved degradability, a surprising reduction in leakage was observed as the pH was adjusted closer to pH 6. These examples illustrate that the present invention can provide improvements in more than one category (in the categories of leakage, degradability, and compatibility). Compared to Comparative Examples 1 and 2, it was observed that better performance and degradability were observed in the presence of a redox initiator (KPS).
[0274] Comparative Example 3
[0275] The aqueous phase containing the acid treated chitosan stock solution was prepared as follows. 96.24 g of Chitosan ChitoClear was dispersed in 2044.09 g of deionized water at 25°C while mixing in a jacketed reactor. The pH of the chitosan dispersion was then adjusted to 5.36 using 42.87 g of concentrated HCl under stirring. The temperature of the chitosan solution was then increased to 65°C within 30 minutes, then to 85°C within 30 minutes, then to 95°C within 30 minutes, and then maintained at 95°C for 2 hours to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid treated chitosan solution. The pH of the chitosan solution was 5.40.
[0276] The oil phase was prepared by mixing 635.63 g of fragrance and 158.92 g of isopropyl myristate with 24.06 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, and then heated to 85° C. in 60 minutes, and then kept at 85° C. for 6 hours, and then cooled to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 10.06 microns.
[0277] Embodiment 11
[0278] The aqueous phase containing the acid and potassium persulfate treated chitosan stock solution was prepared as follows. Potassium persulfate (KPS) solution was prepared by dissolving 0.96g of potassium persulfate in 2056.32g of deionized water at 25°C while mixing in a jacketed reactor. Then 96.43g of chitosan ChitoClear was added to the KPS solution. The pH of the chitosan dispersion was then adjusted to 5.91 using 32.96g of concentrated HCl under stirring. The temperature of the chitosan solution was then increased to 85°C within 60 minutes, and then kept at 85°C for 2 hours to hydrolyze and depolymerize the chitosan. Then after the hydrolysis step, the temperature was reduced to 25°C within a period of 90 minutes to obtain an acid and potassium persulfate treated chitosan solution. The pH of the chitosan solution was 6.04.
[0279] The oil phase was prepared by mixing 636.92 g of fragrance and 159.24 g of isopropyl myristate with 24.11 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, and then heated to 85° C. in 60 minutes, and then maintained at 85° C. for 6 hours, and then cooled to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 33.97 microns.
[0280] Example 12
[0281] A stock solution of acid and potassium persulfate treated chitosan was prepared as follows. 42.08 g of Chitosan ChitoClear was dispersed in 893.0 g of deionized water at 25°C while mixing in a jacketed reactor. 0.42 g of potassium persulfate was added and dissolved. The pH of the chitosan dispersion was then adjusted to 5.87 using 14.40 g of concentrated HCl under stirring. The temperature of the chitosan solution was then increased to 65°C within 30 minutes, then to 85°C within 30 minutes, then to 95°C within 30 minutes, and then maintained at 95°C for 2 hours to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid and potassium persulfate treated chitosan solution. The pH of the chitosan solution was 5.90.
[0282] The aqueous phase was prepared by mixing 433.6 g of the above chitosan stock solution in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of spices and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, and then heated to 95° C. in 60 minutes, and then kept at 95° C. for 4 hours, then 1.38 g of potassium persulfate was added and dissolved, then kept at 95° C. for 2 hours, and then cooled to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 36.25 microns.
[0283] Embodiment 13
[0284] A stock solution of acid and potassium persulfate treated chitosan was prepared as follows. 42.08 g of Chitosan ChitoClear was dispersed in 893.1 g of deionized water at 25°C while mixing in a jacketed reactor. 4.20 g of potassium persulfate was added and dissolved. The pH of the chitosan dispersion was then adjusted to 5.94 using 14.35 g of concentrated HCl under stirring. The temperature of the chitosan solution was then increased to 65°C within 30 minutes, then to 85°C within 30 minutes, and then maintained at 85°C for 2 hours to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid and potassium persulfate treated chitosan solution. The pH of the chitosan solution was 5.36.
[0285] The aqueous phase was prepared by mixing 433.6 g of the chitosan stock solution from Example 13 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, and then heated to 85° C. in 60 minutes, and then maintained at 85° C. for 6 hours, and then cooled down to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 50.79 microns.
[0286] Embodiment 14
[0287] A stock solution of acid and potassium persulfate treated chitosan was prepared as follows. 42.20 g of Chitosan ChitoClear was dispersed in 893.1 g of deionized water at 25°C while mixing in a jacketed reactor. 0.42 g of potassium persulfate was added and dissolved. The pH of the chitosan dispersion was then adjusted to 5.91 using 11.48 g of concentrated HCl and 1.25 g of 90% formic acid under stirring. The temperature of the chitosan solution was then increased to 65°C within 30 minutes, then to 85°C within 30 minutes, then to 95°C within 30 minutes, and then maintained at 95°C for 2 hours to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid and potassium persulfate treated chitosan solution. The pH of the chitosan solution was 5.99. The chitosan stock solution formed was used to prepare the capsules in Examples 14 and 15.
[0288] The aqueous phase was prepared by mixing 433.6 g of the chitosan stock solution from Example 14 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, and then heated to 95° C. in 60 minutes, and then maintained at 95° C. for 6 hours, and then cooled down to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 33.48 microns.
[0289] Embodiment 15
[0290] The aqueous phase was prepared by mixing 433.6 g of the chitosan stock solution from Example 14 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. within 45 minutes, and then heated to 95° C. within 60 minutes, and then maintained at 95° C. for 4 hours, then 1.38 g of potassium persulfate was added and dissolved, then maintained at 95° C. for 2 hours, and then cooled down to 25° C. within 90 minutes. The volume weighted median particle size of the formed capsules was 36.25 microns.
[0291] Example 16
[0292] A stock solution of acid and potassium persulfate treated chitosan was prepared as follows. 42.15 g of Chitosan ChitoClear was dispersed in 893.1 g of deionized water at 25°C while mixing in a jacketed reactor. 0.42 g of potassium persulfate was added and dissolved. The pH of the chitosan dispersion was then adjusted to 5.92 using 8.66 g of concentrated HCl and 2.52 g of 90% formic acid under stirring. The temperature of the chitosan solution was then increased to 65°C within 30 minutes, then to 85°C within 30 minutes, then to 95°C within 30 minutes, and then maintained at 95°C for 2 hours to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid and potassium persulfate treated chitosan solution. The pH of the chitosan solution was 6.01. The chitosan stock solution formed was used to prepare the capsules in Examples 16 and 17.
[0293] The aqueous phase was prepared by mixing 433.6 g of the chitosan stock solution from Example 16 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, and then heated to 95° C. in 60 minutes, and then maintained at 95° C. for 4 hours, then 1.38 g of potassium persulfate was added and dissolved, then maintained at 95° C. for 2 hours, and then cooled down to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 31.68 microns.
[0294] Embodiment 17
[0295] The aqueous phase was prepared by mixing 433.6 g of the chitosan stock solution from Example 16 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, and then heated to 95° C. in 60 minutes, and then maintained at 95° C. for 4 hours, then 3.90 g of potassium persulfate was added and dissolved, then maintained at 95° C. for 2 hours, and then cooled down to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 31.68 microns.
[0296] Embodiment 18
[0297] A stock solution of acid and potassium persulfate treated chitosan was prepared as follows. 156.60 g of Chitosan ChitoClear was dispersed in 3321.0 g of deionized water at 25°C while mixing in a jacketed reactor. 1.57 g of potassium persulfate was added and dissolved. The pH of the chitosan dispersion was then adjusted to 5.93 using 32.05 g of concentrated HCl and 9.29 g of 90% formic acid under stirring. The temperature of the chitosan solution was then increased to 65°C within 30 minutes, then to 85°C within 30 minutes, and then maintained at 85°C for 2 hours to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid and potassium persulfate treated chitosan solution. The solution was combined with 360 g of the stock solution from Example 19 and homogenized. The pH of the chitosan solution was 5.99. The chitosan stock solution formed was used to prepare the capsules in Examples 18 and 19.
[0298] The aqueous phase was prepared by mixing 433.5 g of the chitosan stock solution from Example 18 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, then heated to 85° C. in 60 minutes, then 0.32 g of a 30% hydrogen peroxide (H2O2) solution was added, and then maintained at 85° C. for 6 hours, and then cooled down to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 33.89 microns.
[0299] Embodiment 19
[0300] The aqueous phase was prepared by mixing 433.5 g of the chitosan stock solution from Example 18 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. within 45 minutes, then to 85° C. within 60 minutes, then 0.65 g of a 30% hydrogen peroxide solution was added, and then maintained at 85° C. for 6 hours, and then cooled down to 25° C. within 90 minutes. The volume weighted median particle size of the formed capsules was 30.42 microns.
[0301] Embodiment 20
[0302] A stock solution of acid and potassium persulfate treated chitosan was prepared as follows. 156.55 g of Chitosan ChitoClear was dispersed in 3320.0 g of deionized water at 25°C while mixing in a jacketed reactor. 1.58 g of potassium persulfate was added and dissolved. The pH of the chitosan dispersion was then adjusted to 5.95 using 32.05 g of concentrated HCl and 9.27 g of 90% formic acid under stirring. The temperature of the chitosan solution was then increased to 65°C within 30 minutes, then increased to 85°C within 30 minutes, and then maintained at 85°C for 2 hours to hydrolyze and depolymerize the chitosan. The temperature was then reduced to 25°C over a period of 90 minutes after the hydrolysis step to obtain an acid and potassium persulfate treated chitosan solution. The pH of the chitosan solution was 6.00. The chitosan stock solution formed was used to prepare the capsules in Examples 20 and 21.
[0303] The aqueous phase was prepared by mixing 433.5 g of the chitosan stock solution from Example 20 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, then heated to 85° C. in 60 minutes, then 1.30 g of a 30% hydrogen peroxide solution was added, and then maintained at 85° C. for 6 hours, and then cooled down to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 25.87 microns.
[0304] Embodiment 21
[0305] The aqueous phase was prepared by mixing 433.5 g of the chitosan stock solution from Example 20 in a jacketed reactor. The oil phase was prepared by mixing 128.86 g of the fragrance and 32.22 g of isopropyl myristate with 4.88 g of Takenate D-110N at room temperature. The oil phase was added to the aqueous phase under high shear grinding to obtain an emulsion with the desired particle size. The emulsion was heated to 60° C. in 45 minutes, then heated to 85° C. in 60 minutes, then 3.25 g of a 30% hydrogen peroxide solution was added, and then maintained at 85° C. for 6 hours, and then cooled down to 25° C. in 90 minutes. The volume weighted median particle size of the formed capsules was 25.87 microns.
[0306] Table 8
[0307]
[0308]
[0309] Examples 11 to 21 illustrate the compatibility of delivery particles according to the present invention with substrates such as laundry detergents. These are compared to Comparative Example 3. Examples 12 and 17 (wherein the redox initiator is added to the aqueous phase and to the emulsion) exhibit surprisingly low leakage and substrate compatibility attributes. Such delivery particles according to the present invention will also exhibit favorable degradability attributes. The table further demonstrates that the % aggregate can be adjusted or regulated by the amount of redox initiator introduced, achieving a high level of compatibility attributes when the redox initiator is added to the aqueous phase and / or the emulsion.
[0310] in addition, Figure 4 Describe the differences in charge of delivery particles made according to various treatments (e.g., acid treatment and addition of redox initiators to the aqueous phase or to the emulsion), as described in the examples indicated (i.e., Examples 9, 10, 16, and 18). As shown in the examples, the steps of the present disclosure enable the customization of the zeta potential. For example, the methods of the present disclosure enable the reduction or mitigation of the zeta potential under the pH conditions of use, resulting in more controllable delivery particles that may be usefully less prone to agglomeration in end-use applications and more compatible with the product matrix.
[0311] Capsules according to the invention may have a core to wall ratio of even up to 95 wt % core to 1 wt % wall. In applications where enhanced degradability is desired, higher core to wall ratios may be used, such as 99 wt % core to 1 wt % wall, or even 99.5 wt % to 0.5 wt % or more.
[0312] The shell of the composition according to various embodiments of the invention may be selected to achieve a degradation % target. With appropriate selection of the core to wall ratio, the shell of the composition according to the invention may be selected to achieve a degradation % of at least 40% after at least 60 days when tested according to test method OECD 301B.
[0313] Unless otherwise indicated herein or clearly contradictory to the context, the use of the singular "a", "an" is intended to cover both the singular and the plural. The terms "comprising", "having", "including" and "containing" are interpreted as open terms. All references cited herein (including publications, patent applications and patents) are incorporated herein by reference. Any description of some embodiments as "preferred" embodiments and other descriptions of embodiments, features or ranges as preferred or these are preferred suggestions are not considered to be limiting. The invention is considered to include embodiments that are currently considered less preferred and can be described as such herein. Unless otherwise indicated herein or clearly contradictory to the context, all methods described herein can be performed in any suitable order. Any and all examples or exemplary language (e.g., "for example") provided herein are intended to illustrate the present invention, rather than to impose limitations on the scope of the invention. Any statements herein about the attributes or benefits of the present invention or preferred embodiments are not intended to be limiting. The present invention includes all modifications and equivalents of the subject matter recorded herein as permitted by applicable law. In addition, unless otherwise indicated herein or clearly contradictory to the context, the present invention includes any combination of the above-described elements with all possible variations thereof. The description herein of any reference or patent, even if identified as "existing", is not intended to constitute an admission that such reference or patent is available as prior art against the present invention. Unclaimed language should not be construed as limiting the scope of the present invention. Any statement or suggestion herein that some feature constitutes a claimed component of the present invention is not intended to be limiting unless reflected in the appended claims.
Claims
1. A composition comprising a population of delivery particles, wherein the delivery particle comprises a core and a shell surrounding the core, wherein the core comprises a benefit agent, wherein the shell comprises a polymer material which is a reaction product of modified chitosan and a cross-linking agent, wherein the modified chitosan is formed by treating chitosan with a redox initiator, The redox initiator is selected from the group consisting of persulfates, peroxides, and combinations thereof.
2. The composition of claim 1, wherein the redox initiator is selected from the group consisting of ammonium persulfate, sodium persulfate, potassium persulfate, cesium persulfate, benzoyl peroxide, hydrogen peroxide, and mixtures thereof.
3. The composition of claim 1, wherein the redox initiator and the chitosan are present in a weight ratio of about 90:10 to about 0.01:99.99, preferably about 50:50 to about 1:99, more preferably about 30:70 to about 3:
97.
4. The composition of claim 1, wherein the redox initiator is a persulfate and the shell of the delivery particle comprises a sulfur atom, Preferably, the sulfur atoms are present in the shell at a level of about 0.1% to about 20%, more preferably about 0.1% to about 10%, even more preferably about 0.1% to about 1%, by weight of the shell.
5. The composition according to claim 1, wherein the modified chitosan is formed under acidic conditions at a temperature of at least 25°C, preferably at a pH of 6.5 or less, or even less than pH 6.5, or even at a pH of 3-6.2, or even at a pH of 5-6.
2.
6. The composition according to claim 1, wherein the modified chitosan is an acid-treated modified chitosan, wherein the chitosan is further treated with an acid.
7. The composition according to claim 6, wherein the modified chitosan is acid-treated modified chitosan, wherein the modified chitosan is further treated with a mixture of acids, more preferably a mixture of a first acid and a second acid, wherein the first acid is a strong acid, and wherein the second acid is a weak acid, Preferably, wherein the first acid and the second acid are present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:
35.
8. The composition of claim 1 or claim 6, wherein at least one of the following is true: (a) prior to treatment with the redox initiator and / or acid, the chitosan is characterized by a weight average molecular weight of about 100 kDa to about 600 kDa, preferably about 100 kDa to about 500 kDa, more preferably about 100 kDa to about 400 kDa, more preferably about 100 kDa to about 300 kDa, even more preferably about 100 kDa to about 200 kDa; (b) The modified chitosan is characterized by a weight average molecular weight of about 1 kDa to about 600 kDa, preferably about 5 kDa to about 300 kDa, more preferably about 10 kDa to about 200 kDa, more preferably about 15 kDa to about 150 kDa, even more preferably about 20 kDa to about 100 kDa.
9. The composition of claim 1, wherein the crosslinking agent comprises a polyisocyanate, Preferably, the polyisocyanate is selected from the group consisting of polyisocyanurates of toluene diisocyanate, trimethylolpropane adducts of toluene diisocyanate, trimethylolpropane adducts of xylylene diisocyanate, 2,2′-methylene diphenyl diisocyanate, 4,4′-methylene diphenyl diisocyanate, 2,4′-methylene diphenyl diisocyanate, [diisocyanato(phenyl)methyl]benzene, toluene diisocyanate, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate, 1,4-phenylene diisocyanate, 1,3-diisocyanatobenzene, derivatives thereof, and combinations thereof.
10. The composition of claim 1, wherein the reaction product is formed in a reaction wherein the weight ratio of the chitosan present in the reaction to the cross-linking agent present in the reaction is from about 1:10 to about 1:0.
1.
11. The composition of claim 1, wherein the shell is present in the delivery particle at a level of about 15 wt% or less based on the weight of the delivery particle.
12. The composition of claim 1, wherein the benefit agent is a fragrance material, Preferably the aroma material comprises a fragrance raw material characterized by a logP of about 2.5 to about 4.
5.
13. The composition of claim 11, wherein the core further comprises a partitioning modifier, which is optionally present in the core at a level of about 5% to about 55%, preferably about 10% to about 50%, more preferably about 25% to about 50%, based on the weight of the core, Preferably the partitioning modifier is selected from the following: vegetable oils, modified vegetable oils, C4-C 24 Mono-, di- and triesters of fatty acids, isopropyl myristate, lauryl benzophenone, lauryl laurate, methyl behenate, methyl laurate, methyl palmitate, methyl stearate, and mixtures thereof.
14. The composition of claim 1, wherein the delivery particles are characterized by a volume weighted median particle size of about 1 to about 100 microns, preferably about 10 to about 100 microns, preferably about 15 to about 50 microns, more preferably about 20 to about 40 microns, even more preferably about 25 to about 35 microns.
15. The composition of claim 1, wherein the delivery particle is obtainable from a method comprising the steps of: forming an aqueous phase by treating said chitosan with said redox initiator in the presence of water at a pH of 6.5 or less and a temperature of at least 25° C., preferably for at least one hour and / or until said aqueous phase is characterized by a viscosity of less than 1500 cp, preferably less than 500 cp, to form said modified chitosan, forming an oil phase, the forming step comprising dissolving together at least one benefit agent and at least one crosslinking agent, preferably a polyisocyanate, optionally with added oil, preferably a partitioning modifier; forming an emulsion by mixing the oil phase in an excess of the water phase, preferably under high shear agitation, thereby forming droplets of the oil phase, the droplets being dispersed in the water phase, and optionally adjusting the pH of the emulsion to within the range of pH 2-pH 6; Optionally, providing a second redox initiator to the emulsion, wherein the second redox initiator is the same as or different from the redox initiator added to the aqueous phase; solidifying the emulsion at a temperature of at least 40° C. for a time sufficient to form a shell at the interface of the droplets and the aqueous phase, The shell comprises the reaction product of the cross-linking agent and the modified chitosan, and The shell surrounds the core, which contains droplets of the oil phase.
16. The composition of claim 1, wherein the delivery particle is obtainable from a method comprising the steps of: forming an aqueous phase by treating the chitosan in the presence of water at a pH of 6.5 or less and a temperature of at least 25° C., preferably for at least one hour and / or until the aqueous phase is characterized by a viscosity of less than 1500 cp, preferably less than 500 cp, forming an oil phase, the forming step comprising dissolving together at least one benefit agent and at least one crosslinking agent, preferably a polyisocyanate, optionally with added oil, preferably a partitioning modifier; forming an emulsion by mixing the oil phase in an excess of the water phase, preferably under high shear agitation, thereby forming droplets of the oil phase, the droplets being dispersed in the water phase, and optionally adjusting the pH of the emulsion to within the range of pH 2-pH 6; adding a redox initiator to the emulsion to form the modified chitosan, solidifying the emulsion at a temperature of at least 40° C. for a time sufficient to form a shell at the interface of the droplets and the aqueous phase, The shell comprises the reaction product of the cross-linking agent and the modified chitosan, and The shell surrounds the core, which contains droplets of the oil phase.
17. The composition of claim 1, wherein the delivery particle is cationic, Preferably wherein the delivery particle is characterized by a zeta potential of at least 15 mV at pH 4.
5.
18. The composition of claim 1, wherein the modified chitosan is further modified with a modifying compound, The modifying compound comprises epoxide, aldehyde, α,β-unsaturated compound or a combination thereof.
19. The composition of claim 1, wherein the delivery particle has a core to shell ratio of at most 99: 1, or even at most 99.5:0.5 by weight.
20. The composition of claim 1, wherein the benefit agent is selected from the group consisting of fragrances, flavors, agricultural actives, phase change materials, essential oils, lubricants, colorants, preservatives, antimicrobial actives, antifungal actives, herbicides, antiviral actives, preservative actives, antioxidants, bioactives, deodorants, emollients, moisturizers, exfoliants, UV absorbers, corrosion inhibitors, silicone oils, waxes, bleaching particles, fabric conditioners, malodor reducing agents, dyes, optical brighteners, antiperspirant actives, and mixtures thereof.
21. The composition of claim 1, wherein the delivery particles have a median particle size of 1-200 microns.
22. The composition of claim 1, wherein the shell of the delivery particle degrades by at least 60% within 60 days when tested according to test method OECD 301B.
23. A method of preparing a population of delivery particles, wherein the delivery particles comprise a core and a shell surrounding the core, the method comprising the steps of: forming an aqueous phase by treating chitosan with a redox initiator in the presence of water at a pH of 6.5 or less and a temperature of at least 25° C., preferably for at least one hour and / or until the aqueous phase is characterized by a viscosity of less than 1500 cp, preferably less than 500 cp, to form a modified chitosan, forming an oil phase, the forming step comprising dissolving together at least one benefit agent and at least one crosslinking agent, preferably a polyisocyanate, optionally with added oil, preferably a partitioning modifier; forming an emulsion by mixing the oil phase in an excess of the water phase, preferably under high shear agitation, thereby forming droplets of the oil phase, the droplets being dispersed in the water phase, and optionally adjusting the pH of the emulsion to within the range of pH 2-pH 6; Optionally, a second redox initiator is provided to the emulsion to form the modified chitosan wherein the second redox initiator is the same as or different from the redox initiator added to the aqueous phase; solidifying the emulsion at a temperature of at least 40° C. for a time sufficient to form a shell at the interface of the droplets and the aqueous phase, The shell comprises the reaction product of the cross-linking agent and the modified chitosan, and The shell surrounds the core, which contains droplets of the oil phase.
24. A method of preparing a population of delivery particles, wherein the delivery particles comprise a core and a shell surrounding the core, the method comprising the steps of: forming an aqueous phase by treating chitosan with an acid in the presence of water at a pH of 6.5 or less and a temperature of at least 25° C., preferably for at least one hour and / or until the aqueous phase is characterized by a viscosity of less than 1500 cp, preferably less than 500 cp, forming an oil phase, the forming step comprising dissolving together at least one benefit agent and at least one crosslinking agent, preferably a polyisocyanate, optionally with added oil, preferably a partitioning modifier; forming an emulsion by mixing the oil phase in an excess of the aqueous phase, preferably under high shear agitation, thereby forming droplets of the oil phase dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to within the range of pH 2 to pH 6; adding a redox initiator to the emulsion to form modified chitosan, solidifying the emulsion at a temperature of at least 40° C. for a time sufficient to form a shell at the interface of the droplets and the aqueous phase, The shell comprises the reaction product of the cross-linking agent and the modified chitosan, and The shell surrounds the core, which contains droplets of the oil phase.
25. An article of manufacture comprising a population of core-shell delivery particles according to any one of the preceding claims.
26. The article of manufacture of claim 24, wherein the article is selected from the group consisting of an agricultural formulation, a slurry encapsulating an agricultural active agent, a population of dry delivery particles encapsulating an agricultural active agent, an agricultural formulation encapsulating a pesticide, and an agricultural formulation for delivery of a pre-emergent herbicide.
27. The article of manufacture of claim 25, wherein the agriculturally active agent is selected from the group consisting of agricultural herbicides, agricultural pheromones, agricultural pesticides, agricultural nutrients, insect control agents, and plant stimulants.
Citation Information
Patent Citations
Delivery particle
US20110268802A1
Polyurea Capsules Cross-linked with Chitosan
US20210252469A1
Manifold record material
US2730456A
Oil-containing microscopic capsules and method of making them
US2800457A
Oil-containing microscopic capsules and method of making them
US2800458A